Efficient synthesis of ethyl levulinate from furfuryl alcohol using several biomass-based carbon - Kongde Li; Qikai Si; Guangyu Wu; Guijing Liu; Wei Jiang; Deyang Zhao; Ting Su; Hongwu Zhang; Zhenglong Yang; Christophe Len; Bin He (Biomass and Bioenergy, 2027)

Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

Parametric calibration of a thermo-hydro-mechanical coupled swelling model for viscous soil using Bayesian methods - Changhong Wang; Ting He; Yongqing Wei; Haidong Zhang; Fei Li (European Journal of Environmental and Civil Engineering, 2026)

Development of a sandwich ELISA analysis platform using dual nanobodies for quantitative detection of bovine lactoferrin in dairy products - Li Cao; Ting Zhang; Yan-Ping Li; Qinghua He; Zhui Tu (International Dairy Journal, 2026)

Metabolomics-driven insights into the multi-target antibacterial mechanisms of 2-methoxycinnamaldehyde against Bacillus cereus and its application in pork preservation - Xinrui Li; Renjin Xiang; Yuhan Tan; Fei He; Ting Huang; Jiahao Wang; Kai Yin; Xiaoshan Shi; Yanxiang Wang; Junming Tu; Xian Xia; Jingjing Li (Food Microbiology, 2026)

Thermo-mechanical behavior of medium sandstone under cryogenic conditions: Role of unfrozen water content - Bo Liu; Jie Zhang; Yanhui Han; Ting Li; Lulu He; Lei Gao; Shuhui Li (Cold Regions Science and Technology, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Hypoxia-preconditioned bone marrow mesenchymal stem cells alleviate acute liver failure in association with the VEGF/c-Met pathway - Mei-Mei Lan; Rui-Zhi Shi; Zhe-Yu Li; Wen-Jun Qiao; Yong-Juan Guan; Wen-Qiang He; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Rationally tailoring defect levels in Prussian blue analogues for enhanced rubidium adsorption - Gan Li; Wanghai He; Qiang Li; Fei Xu; Jiazheng Qin; Ting Wang; Mingshan Yang; Xin Hu; Dahuan Liu (Desalination, 2026)

A crystallinity-switch strategy for in-situ encapsulating Pd nanoclusters toward selective conversion of CO2 - Zhao-Cheng Shi; Jing Li; Xue-Feng Zhang; Ming-Ming Wu; Zhonggao Zhou; Meng-Tian Zhang; Chun-Ting He (Chemical Engineering Journal, 2026)

CAMERA: A programmable CRISPR-gated logic system for high-fidelity assessment of Mycobacterium tuberculosis - Jiu Pu; Dan Bai; Yaoyi Zhang; Yiqi Zhang; Li Zhang; Yu He; You Wu; Na Yin; Zhe He; Shun Yao; Ting Xu; Yongchang Wu; et al. (Chemical Engineering Journal, 2026)

Dandelion-like Pd/Cu nanozyme with multi-enzyme activities: A colorimetric sensor array for PFAS discrimination - Hui-ting Hu; Xiao-mei Li; Wen-cai Jiang; Chen Ni; Yu-yang He; Guo-qi Zhang; Hao Yu; Zhi-Bo Hou (Analytica Chimica Acta, 2026)

Integrated analysis of muscle proteomics and neurotransmitter-targeted metabolomics in Penaeus vannamei infected with Enterocytozoon hepatopenaei (EHP) - Zhipeng Yin; Yajie Tian; Chuanyu He; Fan Yang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Aquaculture, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Formation of post-traumatic and non-traumatic knee joint contracture: Role of macrophage polarization in joint capsule and skeletal muscle - Feng Wang; Fan Bai; Ting Zhou; He Liu; Ding-Jiang Wu; Yun Zhou; Wen Li (Tissue and Cell, 2026)

Precursor signal identification of coal rupture based on deformation heterogeneity and acoustic emission in time and frequency domain - Xiangguo Kong; Xuguang Li; Ting Liu; Di He; Zhibo Zhang; Ali Muhammad (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Corrigendum to 'Magnetic and mineralogical evidence for mid- to late Holocene monsoon variability in sediments from Yuehu Lagoon, eastern China' [Palaeogeogr. Palaeoclimatol. Palaeoecol. 698 (2026) 113910] - Menghan Li; Kuang He; Zhaoxia Jiang; Junjie Wu; Ting Hao; Wenhui Li; Xiaohui Zhao; Hanlin Hao; Yuewei Hu; Haonan Song; Fenghui Li; Sanzhong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Gradient sulfur-vacancy engineering of MoS2 for selective non-radical peroxymonosulfate activation: Toward enhanced interference resistance in complex water matrix - Xuexia Guo; Ting Li; Huinan Zhao; Wenbin Huang; Lu Zeng; Zhangnan Yao; Shuanghong Tian; Chun He (Journal of Environmental Chemical Engineering, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Dual-metal-site MOF nanozyme with enhanced activity for highly sensitive colorimetric detection of Cr(VI) in dairy products - Mengyue Gao; Zhiheng Li; Mengjie Liu; Ting He; Xiaolu Su; Yueting Zhao; Zhiqiao Zou; Yanxing Yao; Fengmei Jin; Zhihao Li; Lihua Wang (Food Chemistry, 2026)

Chemotaxonomic significance of dipeptides and flavonoids in the whole plants of Euphorbia dentata Michx - Ye Chang; Tian-Yi Chun; Xue Wen; Xiang-Ting He; Guo-Wei Zhang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Equivalent emissivity correction of the blackbody on-board MWRI-RM - Dong Ke-Song; Xing Rui-Xian; Bai Chuan; XU Jing; Meng Wan-Ting; He Jia-Kai; Jiang Li-Fei (International Journal of Remote Sensing, 2026)

A novel socioeconomic downscaling method by integrating multi-dimensional spatial proximity with multi-source remote sensing data - Wenke Li; Ting Hu; Linxin Li; Yinxia Cao; Wei He (International Journal of Remote Sensing, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

Correction to: Photobiomodulation therapy moderates cancer cachexia‑associated muscle wasting through activating PI3K/AKT/FoxO3a pathway - Yonghua Li; Yibing Chen; Yuan Liao; Ting Huang; Qing Tang; Chengsi He; Liu Xu; Haocai Chang; Hongsheng Li; Quentin Liu; Dongming Lai; Qing Xia; et al. (Apoptosis, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Magnetic and mineralogical evidence for mid- to late Holocene monsoon variability in sediments from Yuehu Lagoon, eastern China - Menghan Li; Kuang He; Zhaoxia Jiang; Junjie Wu; Ting Hao; Wenhui Li; Xiaohui Zhao; Hanlin Hao; Yuewei Hu; Haonan Song; Fenghui Li; Sanzhong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Complete genome sequence of a novel Pseudomonas sp. GW-45 isolated from Antarctic Ardley cove showing DMSP degradation capability - Yi-He Zhang; Yong-Qiang Hu; Zuo-Qi Wang; Chun-Yang Li; Ting Hu; Zhong Hu; Yin-Xin Zeng (Marine Genomics, 2026)

Transcriptome analysis provides molecular evidence for muscle growth regulation in Litopenaeus vannamei infected with Ecytonucleospora hepatopenaei (EHP) - Chuanyu He; Zhipeng Yin; Yajie Tian; Fan Yang; Zheng Cao; Cuixia Wang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Journal of Invertebrate Pathology, 2026)

A synthetic microbial community for the enhanced removal of complex emerging pollutants from domestic wastewater - Ting Xu; Hui Yun; Yuru Zhao; Yue He; Siyu Chen; Ting Ma; Wenjie Zhang; Liang Peng; Xiangkai Li (Journal of Hazardous Materials, 2026)

Freeze-dried chocolate as a one-bite carrier for calcium, magnesium and vitamin D3: uniform codelivery with enhanced stability, instant disintegration and site-specific release - Qianqian Li; Lu Yang; Ting Xu; Yuhui Wang; Lulu Zhang; Juan Hao; Yuwei He; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2026)

UEV1A attenuates MDA5-mediated antiviral immune response by reducing its ubiquitination and aggregation - Jiaxin Wang; Rongyao Sun; Ting Li; Houcheng Liang; Huan He; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Nano-confined MXene/covalent organic framework photothermal bioreactors for efficient catalysis and temperature control - Chen-Xi He; Hui-Ting Li; Jia-Ying Chen; Zhen-Feng Zhang; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Bioresource Technology, 2026)

Interdecadal intensification of late-spring precipitation over the Hengduan Mountains since the late 1990s - Meiying Zheng; Huizhi Liu; Shengyuan Liu; Haoran Li; Xiaoyang Liu; Lijun Xie; Guotao Zhang; Ting Yang; Fei Wang; Yunhao Gu; Junjie Zhao; Shuo He (Climate Dynamics, 2026)

Comprehensive Transcriptomics and Biochemical Analysis Provide New Insights into the Light Intensity Regulation Growth and Medicinal Quality of Dendrobium nobile - Ting Li; Haolin Liu; Yijun Fan; Hui Wang; Linlong Xu; Siyu He; Jie Ma; Junlan Wu; Chunhong Mou; Meng Zhao; Li Chen; Xuyang Liu; et al. (Journal of Plant Growth Regulation, 2026)

Multi-omics, machine learning, and molecular simulation identify CD44 as a candidate target in endocrine-disrupting chemical–associated thyroid cancer progression - Yifan Hu; Keshu Liu; Ting Chen; Zhizhen He; Shuang Li; Wu Hu; Qiuyang Fu; Xiong Chen (Molecular Diversity, 2026)

A multi-model dynamic adaptive fusion model for irregular wave forecasting - Menghua Li; Guanghua He; Zhengxiao Luan; Ting Cui; Dongrui jiang; Chaogang Liu; Chuankai Zhao (Ocean Engineering, 2026)

Gut dysbiosis and Escherichia coli-associated enrichment of antibiotic resistance genes in diarrheal yak calves - Ze Cao; Huanyu Gong; Huilin Qin; Ting Wei; Xiaoqiang He; Kairi Yang; Xiaowei Li; Yanwen Wang; Yunqiang Jia; Xi Lan; Wen He; Xiaoping Jing; et al. (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Wet-grinding carbonation of concrete slurry waste under low-concentration CO2 for preparing low-carbon foam concrete - Jin Yang; Hao Zheng; Maogao Li; Ying Su; Ting Li; Bohumír Strnadel; Tesfaye Alemu Mohammed; Xingyang He (Journal of Environmental Management, 2026)

Better representation of linear features in species distribution models: Mapping the distribution of the Scaly-sided Merganser (Mergus squamatus) - Yangsirui Zhang; Peizhong Liu; Lixing Gu; Li Wen; Ying He; Zijian Wang; Liangjun Zhou; Ting Lei; Cai Lu; Qing Zeng; Guangchun Lei (Journal of Environmental Management, 2026)

A Global Meta-analysis of Minerals in Human Milk: Quantifying Variations by Lactation Stage, Geography, and Analytical Method - Nan Li; Ting Li; Yuqi Huang; Liufeng Zheng; Jian He; Sufang Duan; Jing Li; Zeyuan Deng (International Dairy Journal, 2026)

Maternal Bifidobacterium bifidum BD-1 supplementation during late gestation modulates offspring gut microbiota succession and responses to DSS-induced acute colitis in a delivery-mode-dependent manner - Chenrui Peng; Chang Lu; Xiaoting Li; Lunpu Zhang; Yao Zeng; Xiaona Wu; Ting Wu; Fang He; Xi Shen (Food Bioscience, 2026)

Iodine vacancy-engineered BiOI steering selective singlet oxygen generation for high-flux antibiotic degradation with peroxyacetic acid activation - Yuchen Chu; Ting Zhou; Yuxi Zeng; Siying He; Jiawei Yue; Wenjun Wang; Yang Yang; Ziwei Wang; Fanzhi Qin; Hongda Liu; Xiaoming Li; Jie Liang; et al. (Chemical Engineering Journal, 2026)

Innovative technologies and future perspectives in tumor microbiomics - Wan-Ting He; Xiaofang Xing; Fei Wang; Le Li; Ye Cheng; Gang Yao (Science China Life Sciences, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

Integrated Transcriptomic and Proteomic Analysis Reveals the Immune Response of Largemouth Bass ( Micropterus salmoides ) to Aeromonas hydrophila Infection - Fuyan Chen; Shuiping Wen; Xuehai He; Aiying Lei; Ting Huang; Yushan Wu; Honglian Tan; Youyong Liang; Xiaohua Lu; Meizhen Su; Jianbin Li; Xianhua Ouyang (Journal of Fish Diseases, 2026)
Largemouth bass ( Micropterus salmoides ) is an economically important freshwater fish species in China that is frequently affected by disease outbreaks caused by Aeromonas hydrophila . This study employed an integrated transcriptomic and proteomic approach to investigate the response of the liver in largemouth bass at 72 h post‐infection with A. hydrophila via intraperitoneal injection. We identified differentially expressed genes (DEGs; 2136 upregulated and 200 downregulated) and differentially expressed proteins (DEPs; 1683 upregulated and 1817 downregulated). Functional enrichment analysis indicated that the upregulated DEGs/DEPs were significantly involved in immune and inflammatory responses, encompassing pathways, such as TNF signalling, NF‐kappa B signalling, complement and coagulation cascades and B cell receptor signalling, while the downregulated DEGs/DEPs were primarily associated with metabolic processes, especially lipid metabolism. Integrated transcriptomic and proteomic analysis identified 420 correlated DEG/DEP pairs, among which 154 were consistently upregulated and 19 consistently downregulated. The upregulation of eight key immune‐related DEG/DEPs, including complement components (C1q, C7b, C1r‐A), MYD88 and BCL10, was verified by RT‐qPCR. Collectively, these findings provide valuable insights into the molecular basis of immune defence against A. hydrophila in largemouth bass and identify potential immune‐related biomarkers that may be useful in the development of effective prevention and control strategies.

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

Effects of Different Dietary Inclusion Levels of Soybean Meal Supplemented with Crystalline Amino Acids on Mineral Deposition in Different Tissues of Weaned Piglets - Luqi Cai; Ting Yao; Liuqin He; Yulong Yin; Tiejun Li (Biological Trace Element Research, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

PM2.5-bound organophosphate esters and childhood attention-deficit hyperactivity disorder symptoms: A population-based study from China - Chu Chu; Xuan Liu; Yan-Xu Chen; Jia-Xiang Dong; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Xia Liang; Yang Zhou; Muhammad Amjad; Yan Yang (NeuroToxicology, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

First-trimester profiling of maternal plasma metals and vitamins in relation to gestational hypertension - Ting Wu; Tao Li; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Environmental Research, 2026)

Long-term stability and environmental safety of in-situ stabilization combined with micro-fertilization for cadmium mitigation in a soil-rice system: A four-year field experiment - Liqin He; Ziyao Li; Min Nie; Ting Li; Yuepeng Yin; Zhihong Guo; Jiufang Du; Jibin Yin; Taolin Zhang; Changfeng Ding (European Journal of Agronomy, 2026)

Electronic tuning of δ-MnO2 via interlayer Ag+ for efficient ozone decomposition under humid conditions - Ting Li; Zhongyu Wang; Xinyao Lei; Yuyan He; Minghao Shi; Mingjia Zhang; Shule Zhang; Qin Zhong (Chemical Engineering Journal, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Response of greenhouse gas emissions, nitrogen loss and microbial communities to the presence of conventional and biodegradable microplastics in soil - Wenxu Li; Mengxiao Li; Jiaju He; Zhenyu Huang; Jian Zeng; Christopher W.N. Anderson; Minghua Zhou; Cheng Zhang; Xuesong Gao; Di Zhao; Ting Lan (Applied Soil Ecology, 2026)

Optimized Nitrogen Reduction Enhances Biomass Accumulation and Nitrogen Uptake of Maize–Soybean Intercropping Systems by Modulating Root Morphological Plasticity and Rhizosphere Enzymatic Activities - Ting Li; Jiao Wu; Liang He; Le Kang; Rina Wu; Yun Xiang; Jianmin Li (Journal of Soil Science and Plant Nutrition, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Amino acid and appendicular skeletal muscle mass insufficiency are associated to cognitive decline in Chinese population - Ting Tang; Shuxian Zhang; Yanni Pu; Siquan Li; Bin Jiang; Huiting Liang; Kunmu Zheng; Yan Zheng; He Huang; Jin Li; Xiaodong Pan (GeroScience, 2026)

Four new cysteine derivatives with cytotoxic activity from Poecilobdella manillensis - Qingqing Fan; Peixing He; Hang Xiao; Juan He; Ting Wang; Zhenbei Lan; Feng Tian; Jianyuan Tang; Li Ma (Phytochemistry Letters, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Risk assessment, source apportionment and driving mechanism of soil heavy metals in coal mining areas of Xinjiang, China - Xin He; Fei Zhang; Ting Zhou; Boyu Wang; Xuan Zhang; Xiangyu Liu; Zia Ahmed; Mou Leong Tan; Ziheng Feng; Zhihui Li; Xu Ma (Gondwana Research, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Active site-directed tandem catalysis on Pt-loaded nitrogen-rich carbon for driving piezo-synthesis of hydrogen peroxide and in-situ utilization for emerging contaminants removal - Huinan Zhao; Ting Li; Wei Liu; Kaiwen Wang; Yanhong Lu; Lu Zeng; Jia He; Lingling Hu; Chun He (Chemical Engineering Journal, 2026)

Flexible tactile sensing systems: Material innovations, fabrication strategies, and intelligent applications in human-machine interfaces - Xingfeng Zhao; Yangyang Pei; Maomao He; Fangli Wang; Ting Liu; Shoujia Zhu; Xiaoyan Li; Yue Li; Bin Liu; Hongjian Zhang; Linghai Xie; Wei Huang (Chemical Engineering Journal, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Structural decomposition enables multi-omics dissection of common and organ-specific aging - He Huang; Yi Li; Qinglin Song; Liyun Yuan; Yuqi Yang; Minwei Zhu; Renliang Sun; Yue Hu; Chenyihang Xiong; Ting Ni; Yun Liu; Andrés Ruiz-Linares; et al. (Science China Life Sciences, 2026)

Biocontrol of tobacco bacterial wilt by Bacillus velezensis Y19: insights into chemotaxis, competition and antagonism - Yajie Hu; Xiaolan Yang; Huiping Wu; Qunling Li; Guangxiong Xiao; Feng Wu; Feng Li; Zihua He; Xiaoxing Lin; Ting Ding (Physiological and Molecular Plant Pathology, 2026)

Waste-derived elastic carbon catalysts for integrated CO2 capture and cycloaddition to cyclic carbonates - Ting Wang; Zhipeng Ren; Wenyu He; Fan Zhang; Kyung Hoon Min; Byeongseok Kim; Sang Eun Shim; Denian Li; Yingjie Qian; Haoran Yuan (Journal of Hazardous Materials, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

A high-performance LaSA-Co MAs catalyst derived implantable flexible electrochemical sensor for endogenous dopamine detection - Binqi He; Jiawei Li; Qianzuo Liu; Xinyue Xiang; Sifan Sun; Haoran Yang; Guosheng Cheng; Maiyong Zhu; Ying Hao; Ting Zhang; Tie Li (Chemical Engineering Journal, 2026)

Manipulating non-radical pathway preference in PMS-mediated phenolic degradation: Substituent-dependent catalyst-pollutant interfacial interaction over single-atom Fe-N-C - Fan Huang; Xianhu Long; Ting Li; Xuexia Guo; Lingling Hu; Huinan Zhao; Shuanghong Tian; Minhua Su; Chun He (Chemical Engineering Journal, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Microneedle-mediated delivery of hydroxypropyl-β-cyclodextrin-encapsulated Angelica sinensis (Danggui) essential oil for acne treatment: efficacy and mechanisms - Xiaoli Liu; Xiaojuan Li; Weijun He; Xiaoyu Han; Ting Xiao; Shiqi Guo; Yujie Jia; Liqun Lin; Ming Yang; Li Wang; Yuehong Xu (Drug Delivery and Translational Research, 2026)

Magnetite in lunar impact glasses formed in the presence of water - Ting Li; Jieqi Xing; Yang Li; John A. Tarduno; Xuelin Zhu; Zelong Shi; Ye Zheng; Qian He; Ziying Li; Sheng He; Jun Zhong; Liumin Deng; et al. (Science Bulletin, 2026)

Efficient nitrate and ammonium removal by psychrotolerant strain Pseudomonas yamanorum EH-G3 under acidic conditions - Qifeng Wu; Ruoyu Li; Ting Zou; Mei Li; Jianguo Zou; Tengxia He (Journal of Environmental Chemical Engineering, 2026)

Remediation of cadmium-contaminated soils by mercaptosuccinic acid-intercalated hydrotalcite: Effects on soil quality and cadmium accumulation in rice - Liqin He; Changfeng Ding; Min Nie; Ting Li; Ziyao Li; Taolin Zhang; Yurong Wang; Xingxiang Wang (Journal of Environmental Management, 2026)

Microwave melting of lunar regolith simulant in an unchambered environment: Insights from physical model experiments - Jia-Qi Lu; Zheng-Wei Li; Xia-Ting Feng; Cheng-Dan He; Yong-Jun Wang; Yang Zuo; Jin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Sibakazin: a novel black fly derived non-classical kazal protease inhibitor, targeting antiplatelet (P2Y12/GPVI) pathways without perturbing coagulation - Zhuorui Li; Yanmei He; Yan Shen; Miao He; Ting Lin; Jiayi Yang; Lixian Mu; Jing Wu; Hailong Yang (Insect Biochemistry and Molecular Biology, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Potential contribution of terrestrial plants in the marginal sea food web: Evidence from in situ diet of the pelagic copepods in the South China Sea - Haoyang He; Lianming Zheng; Senjie Lin; Ling Li; Peihao Liu; Ting Li; Zhidi Gong (Marine Pollution Bulletin, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Integrated machine learning and density functional theory to design C₃N₅ piezo-catalysts toward precise control of selective reactive oxygen species and efficient water purification - Ting Li; Xianhu Long; Wei Liu; Fan Huang; Huinan Zhao; Tao Zhong; Jingyun Fang; Chun He (Journal of Hazardous Materials, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Dynamic modeling of competitive growth between Listeria monocytogenes and background microbiota in Flammulina velutipes - Sijie He; Xuejie Liu; Qing Yu; Yangyang Xu; Ting Fang; Yeru Wang; Changcheng Li (Food Control, 2026)

Early predicting brain metastases of EGFR positive lung adenocarcinoma patients by CT radiomics - Xinliu He; Chao Guan; Ting Chen; Houde Wu; Liuchao Su; Mingfang Zhao; Li Guo (Physical and Engineering Sciences in Medicine, 2026)

Alisol B 23-acetate alleviates high-fat diet-induced insulin resistance by activating the SIRT1/FOXO1 axis and PI3K/AKT pathway - Wenjun He; Zhenxuan Kong; Jingshu Cai; Zhuyun Wang; Li Ma; Xiaoqiu Xiao; Ting Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Physiological and Secondary Metabolism of Dendrobium nobile Lindl in Response to High Temperature Stress - Linlong Xu; Yijun Fan; Xueyan Tan; Jie Ma; Ting Li; Siyu He; Hui Wang; Liangjie Zhu; Le Zeng; Aoxue Luo (Journal of Plant Growth Regulation, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Soil phosphorus dynamics during cropland reforestation - Wenchao Wu; Rongxiao Che; Song Zhang; Yunlong He; Benjamin L. Turner; Dong Liu; Fang Wang; Ting Li; Anquan Xia; Zejin Zhang; Tong Li; Guangbing Xu; et al. (Agriculture, Ecosystems & Environment, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

Magnetically controlled delivery capsule endoscopy for precise drug delivery to intestinal lesions - Chen He; Xi Jiang; Ting Zhang; Yizhi Chen; Xiaoou Qiu; Zhaoshen Li; Zhuan Liao (Drug Delivery and Translational Research, 2026)

Multiomics approaches identify immunometabolic crosstalk in triploid cyprinid fish after Edwardsiella tarda 1 l-4 infection - Ruo-Xing Yu; Ting Luo; Qin-Yang He; Zi-Rou Zhong; Jie Peng; Yao-Hui Li; Zhuang-Wen Mao; Ming-Zhu Huang; Zi-Le Qin; Xu-Ying Kuang; Zi-Xuan Fang; Jian Li; et al. (Aquaculture, 2026)

Formation of residual water in sandstone CO2-H2O system: A comprehensive study based on orthogonal experiment and nuclear magnetic resonance method - Yi Li; Wendong Dan; Yujie Diao; Li He; Ting Liu (Journal of Hydrology, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Socioeconomic inequality in flood exposure and compound urban flood risk: A multistage assessment across 30,000 towns in China - Zhen He; Jinghao Hei; Zhiqiang Wu; Otthein Herzog; Lan Li; Ting Yang; Xiang Li (Journal of Environmental Management, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Progressive uncertainty-guided network for binary segmentation in high-resolution remote sensing imagery - Jiepan Li; Wei He; Ting Hu; Minghao Tang; Liangpei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Te-Cu dual adsorption-conversion function cathode enables high-energy-density and long-lifespan liquid metal batteries - Weixin Zhang; Xin He; Ting Zhang; Haomiao Li; Shuai Yan; Xianbo Zhou; Yewei Guo; Min Zhou; Wei Wang; Kai Jiang; Kangli Wang (Chemical Engineering Journal, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Design, synthesis and activity evaluation of usnic acid monoesterification derivatives - Qing Zhang; Jun-Li He; Xiao-Xia Zhuo; Yi-Meng Hao; Hong-Ting Duan; Yan Jia; Jing-Jing Wang; Li-Ning Wang (Natural Product Research, 2026)

Saline patch identification using a semi-supervised knowledge integration deep learning framework based solely on UAV RGB imagery - Zhen Li; Zhigang Sun; Ting Yang; Zhen Liu; Wentao Sun; Yixuan Zhang; Jundong Wang; Yajuan He; Zeqian Yang; Wei Han (Computers and Electronics in Agriculture, 2026)

Simultaneous transformation of tetracycline and nitrogen (ammonium/nitrite) by Sphingobacterium kyonggiense T8: Performance, pathway, genomics, and mechanisms - Yifei Leng; Yangqi Peng; Huan He; Ting He; Fengyi Chang; Wen Xiong; Zhu Li (Journal of Hazardous Materials, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Decorating the bridge in through-space charge-transfer emitter with an electron-withdrawing group for facile synthesis, tunable emission/transport property and improved electroluminescence performance - Yan Shu; Dajun Zhuang; Ting Li; Zetian Wang; Yongjun Song; Lei He (Chemical Engineering Journal, 2026)

Straw-induced hematite-to-magnetite conversion in alkaline media: Experimental study and potential in Bayer process - Xin He; Guo-zhi Lv; Bing-shen Liu; Qing-dong Li; Xiao-lei Zhang; Zhuang-zhuang Yun; Ting-an Zhang (Minerals Engineering, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Photodegradation of sulfisoxazole during nitrite-sensitized photolysis - Xu Gao; Xiaoyu Li; Yaowu Xu; Xinyu Zhan; Ting Zhou; Bing Zhou; Xin Wang; Yuhang He; Chunyu Wang; Han Mao (Journal of Environmental Chemical Engineering, 2025)

Automatic immunomagnetic beads clean-up coupled with HPLC-FLD for rapid, simple and high-throughput detection of zearalenone in cereal foods and feeds - Zhiming Xiao; Jun Zhang; Yinji Jin; Bo He; Ting Yao; Jing Tian; Fan Mo; Decheng Suo; Shi Wang; Runxian Li; Lijie Zhang; Shen Hu; et al. (Food Chemistry, 2025)

Human milk fat Substitutes alleviate dextran sulfate sodium induced cognitive deficits in mice by modulating brain fatty acid and ether Lipid metabolism - Yangzheng He; Linhui Zeng; Han Liao; Jing Li; Yong Sun; Hongyan Li; Ting Luo; Zeyuan Deng (Food Bioscience, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Association between short-term exposure to ambient fine particulate matter & components and the risk of spontaneous abortion - Jialiang He; Wenzheng Zhou; Xin Ming; Yunping Yang; Ziyi He; Yannan Li; Ting Dong; Xinzhen Chen; Min Zhang; Yankun Wang; Yubin Ding; Wei Zhou (Atmospheric Pollution Research, 2025)

Identification of AhFPA1 as the causal gene underlying qEFT13.1, a key QTL for early flowering in peanut - Zhao Li; Yu Liu; Qingliang Hu; Jiahao Liang; Zehua He; Yixin Wang; Wenrui Zhang; Ting Pan; Gonghao Ma; Jing Wang; He Zhang; Zhenghao Lv; et al. (Theoretical and Applied Genetics, 2025)

Mechanism of Axial Chain Rockbursts in Deep Tunnels: Structural Plane-Induced Stress Concentration Triggered by Drilling and Blasting - Hong-Pu Li; Ben-Guo He; Xia-Ting Feng; Wen-Jing Niu; Tao Ma (Rock Mechanics and Rock Engineering, 2025)

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

Comparative analysis of the WRKY gene family between Chimonanthus praecox and C. salicifolius - Wei Zou; Gui-Ting Hu; Fang-Fang Gui; Xin-Chen He; Priyanka Borah; Li Zhu; Hui-Juan Ning; Li-Yuan Yang (Genetica, 2025)

Retraction Note: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Deep learning-based tunnel advance geological forecast for polygon targets via regional GPR data - Ting-wei Yang; Jing-he Li; Ye-hui Cao; Bin Xiong; Liu-ye Wei (Applied Geophysics, 2025)

Aeromagnetic characteristics and lithologic mapping in Panzhihua-Anyi area - Jiao-jiao Li; Yong-jun Zhang; Yi-yuan He; Ting-yan Zhao; Shi-jun Li (Applied Geophysics, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Co-optimization of distributed energy systems: A three-layer framework leveraging a novel diagram-driven method - Junquan Guan; Weike Mo; Yongyi Li; Weiliang Wang; Ting He; Chang Huang (Journal of Cleaner Production, 2025)

Solar radiation on complex underlying surfaces in Xinjiang: A typical arid and semi-arid region in the northwestern China - Chengming Zhang; Xin Liu; Shuyi Chen; Jianrong Bi; Yonghang Chen; Qing He; Ting He; Yunhong Xu; Hui Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Nitrogen transformation in the crop-soil system determines the exacerbation of yield-scaled N2O emissions from rice paddies under climate change - Yuanyuan Wang; Wei Huang; Ziqi Xu; Zhenghua Hu; Tingwu Liu; Guihua Lu; Kezhi Zheng; Dan Dong; Yonggang Xu; Shuqi He; Gecong Ma; Ting Li; et al. (Field Crops Research, 2025)

Humid heat’s nonlinear impact on school-age children’ sleep health: Evidence from Guangdong, China - Yuan Gao; Li-Zi Lin; Wen-Wen Bao; Wan-Ting He; Yun-Ting Zhang; Guang-Hui Dong; Shenjing He (Environmental Research, 2025)

IFNγ-exosomes accelerate wound healing by suppressing immune rejection of allogeneic keratinocytes in collagen/PRP scaffolds via the IDO-kynurenine pathway - Shijie Song; Weidong Zhang; Wei Ji; Ting Li; Kai Guo; Xiang He; Dahai Hu; Huilin Liu; Yunchuan Wang (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Optimizing hematite reduction in high - Iron bauxite during Bayer process via bagasse: A path to efficient resource utilization - Xin He; Guo-zhi Lv; Xiao-lei Zhang; Qing-dong Li; Bing-shen Liu; Zhuang-zhuang Yun; Ting-an Zhang (Biomass and Bioenergy, 2025)

UV-guided separation of polyacetylenol glycosides from the edible roots of Codonopsis pilosula and their anti-inflammatory activity - Xilan Jiang; Lun Wang; Yao Chen; Yi Zuo; Mengdan Liu; Bin Chen; Dong Fu; Yujiao He; Mingkui Wang; Ting Shen; Fu Li (Phytochemistry, 2025)

Maillard reaction based chitosan-monosaccharide films and the application in fruit preservation - Panpan Zhao; Danping Zheng; Ting Li; Haoyang Peng; Jiaqi He; Jinyi Shi; Jinzhong Zhao; Peng Li; Wuxia Zhang (Food Hydrocolloids, 2025)

Impact of system size on pattern transitions in dissolving rough fractures: experiments, multi-physics coupling simulations and theoretical analysis - Ting Wang; Yaning He; Yanlong Li; Ran Hu; Yang Zhou; Yifeng Chen; Junrui Chai; Yunhe Liu (Computers and Geotechnics, 2025)

The PRIDE system: A photo-responsive platform for high-efficiency isolation of extracellular vesicles for Parkinson's disease diagnostics - Wenjing Zhang; Ting Zhang; Jiayu Ding; Jingwen Cao; Zheyan He; Yanling Liu; Yong Juan Zhao; Chungen Qian; Chenzhong Li; Jiasi Wang; Bo Peng; Cheng Jiang (Chemical Engineering Journal, 2025)

Preparation of N-doped porous biochar with high CO2 adsorption performance via one-step molten salt thermal treatment - Tian Xie; Jing He; Liang-Chen Xu; Ting Yan; Quan-Wen Pan; Li-Wei Wang; Wei-Guo Pan (Chemical Engineering Journal, 2025)

Unveiling the vertical dynamics of atmospheric ammonium in Asia megacity: A GRASP-based investigation of spatiotemporal patterns and source drivers - Yining Tan; Ting Yang; Hongyi Li; Ping Tian; Yifan Song; Jiancun He; Yutong Tian; Yele Sun; Zifa Wang (Atmospheric Research, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Transcriptome Reveals Molecular Characteristics and Immune Response in Triploid Cyprinid Fish Infected with a Novel Pathogenic Aeromonas sp. AS1-4 - Qin-Yang He; Jie Peng; Ruo-Xing Yu; Ting Luo; Yao-Hui Li; Zi-Rou Zhong; Zi-Le Qin; Fei Wang; Jian Li; Sheng-Wei Luo (Marine Biotechnology, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Innovative starch-based alkaline thermal reduction of hematite: A fundamental study on mineral phase reconstruction and its potential in the Bayer process - Xin He; Guo-zhi Lv; Song Wang; Qing-dong Li; Zhuang-zhuang Yun; Ting-an Zhang (Minerals Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

ZmDof08, a zinc finger transcription factor, plays critical roles in photosynthesis in maize - Ting Li; Jinjie Guo; Jiahao Zhang; Ping Deng; Yuanyuan Xu; Xinjia Li; Yu He; Lian Zhou; Chaofeng Li; Chaoxian Liu (Plant Cell Reports, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Phase and defect engineering of 1T/2H MoS2-x nanosheets for enhanced piezocatalytic inactivation of antibiotic-resistant bacteria - Huinan Zhao; Zhangnan Yao; Ting Li; Yanhong Lu; Kaiwen Wang; Jia He; Shuanghong Tian; Fan Huang; Chun He (Journal of Hazardous Materials, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

High value-added conversion of atmospheric pollutants and greenhouse gases: assessment of bottlenecks and optimization strategies for mainstream catalytic technology - Tao Zhong; Xianhu Long; Zhangnan Yao; Ting Li; Huinan Zhao; Su Tang; Shuanghong Tian; Chun He (Journal of Cleaner Production, 2025)

Efficiently hydrogenolysis of aromatic ether C-O bonds in lignite and model compounds over carbon-coated NiCo bimetallic catalyst - Caitao Chen; Juan Ma; Yakun Tang; Xiaohui Li; Guangbo Liu; Hanyao Song; Yingluo He; Noritatsu Tsubaki; Lang Liu; Ting Liu (Fuel, 2025)

Lacticaseibacillus paracasei NCU-21 improves ethanol-induced gastric mucosal injury by regulating the Nrf2/HO-1 signalling pathway and gastrointestinal microbiota in mice - Jie You; Xinyi Zhang; Leiping Ding; Yifeng Yu; Qingling Yang; Tangchang Xu; Zhipeng He; Ting Li; Jing Wei; Tingtao Chen (Food Research International, 2025)

MgFe-LDHs/Vallisneria natans combined system for simultaneous elimination of endogenous N and P pollution in eutrophic water: Performance, synergetic mechanism, and metagenomics analysis - Zihao Hu; Zeyu Li; Yin Xu; Feifei He; Jiani Zhang; Ting Li (Environmental Research, 2025)

Prim-O-glucosylcimifugin-loaded nanodrug hydrogel alleviates periodontitis and colitis via modulating macrophage polarization and microbiota balance - Chengye Ding; Xinjia Cai; He Zhang; Yixin Ma; Liyuan Chen; Xiaolan Wu; Min Yu; Chang Li; Hangbo Liu; Shiying Zhang; Xinmeng Shi; Ting Zhang; et al. (Chemical Engineering Journal, 2025)

CD73 polymorphisms are associated with schizophrenia - He-Xia Peng; Li-Li Zhang; Dan Jiang; Na Jian; Ting-Mei Zhang; Jia-Guo Luo; Hai-Yan Yin (Purinergic Signalling, 2025)
Ecto-5’-nucleotidase/CD73 enzyme plays a key role in the regulation of extracellular adenosine levels, thereby exerting influence on adenosine homeostasis. Emerging evidence suggests that perturbations in purines and ecto-5’-nucleotidase activity are associated with an augmented susceptibility to schizophrenia. However, the precise impact of genetic variations in CD73 on individuals with schizophrenia remains poorly understood. Here, our study demonstrated that rs3734442 allele and rs4431401 heterozygote were conferred a significant risk of schizophrenia disease (rs3734442: odds ratio, 0.556; 95% CI, 0.375 to 0.825; p = 0.004; rs4431401: odds ratio, 1.881, 95% CI, 1.117 to 3.166; p = 0.020). Comparing different genders, we observed a significant association between rs3734442 genotypes and male cases (rs3734442: odds ratio, 0.452; 95% CI, 0.257 to 0.796; p = 0.007). Likewise, there was a significant association between rs4431401 genotypes and male patients (rs4431401: odds ratio, 2.570; 95% CI, 1.196 to 5.522; p = 0.015). Based on family history and antipsychotics medication usage, our data reveals that the rs9444348 allele exhibits the most significant association with familial susceptibility to schizophrenia (odds ratio, 1.541; 95% CI, 1.009 to 2.353; p = 0.048 for A vs G). Moreover, individuals carrying variants of rs6922, rs2229523, and rs2065114 while being treated with clozapine demonstrate a higher frequency proportion compared to those receiving risperidone treatment ( p = 0.035; p = 0.049; p = 0.027 respectively). Additionally, our results indicate that patients with GG genotype of rs9444348 had significantly higher likelihood of using clozapine instead of sulpiride ( p = 0.048). Overall, our data strongly suggest that genetic variations in CD73 are significantly associated with schizophrenia risk and may serve as valuable resources for identifying therapeutic targets.

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Not for nothing, microplastics can (potentially) reduce the risk of mosquito-to-human transmission of arboviruses - Jian-hang Li; Xiao-hui Liu; He-ting Gao; Guo-rui Liang; Teng Zhao; Chun-xiao Li (Journal of Hazardous Materials, 2025)

Designing stable walnut oil Pickering emulsions: Interfacial behavior and zero-order release of stigmasterol and β sitosterol using walnut protein-high methoxyl pectin-gallic acid complexes - Xu Zhang; Xiaoqian Zhan; Ruonan He; Honghong Zhang; Yazhuan Li; Wenyu Liu; Ting Wang; Ting Zhang; Changqing Wei (Food Chemistry, 2025)

Mixed-cation engineering of hybrid antimony chlorides for band gap-directing deep-blue emission - Ren-Jie He; Lin-Xia Yang; Xin-Yu Ma; Ting-Jie Wang; Zengsheng Guo; Jinling Miao; Suna Wang; Cuncheng Li; Guang-Ning Liu (Chemical Engineering Journal, 2025)

Concentration-dependent effects of polystyrene microplastics on methanogenic activity and microbial community shifts in sewer sediment - Lucheng Li; Ting Xiao; Zanji He; Qijin Chen (Bioresource Technology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Assessing sensitivity and uncertainty in rod ejection accidents: A combined PCE-POD approach - Yijun Zhang; Wenhuai Li; Sitao Peng; Jinggang Li; Ting Wang; Qingyun He; Tao Wang; Haoliang Lu; Zeng ling (Annals of Nuclear Energy, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Endothelial GTPBP3 directs developmental angiogenesis and neovascularization after limb ischemia via the mtROS/HRl/ATF4/mTORC1 axis - Donglu Qin; Jiarui Hu; Yang Yang; Xin Li; Jia He; Jin Chen; Xin Guo; Cheng Wei; Fengjiao Wang; Ting Yi; Chenyu Li; Bilian Yu (Angiogenesis, 2025)

Effects of Maternal Trace Elements Exposure in Early Pregnancy on Maternal Thyroid Hormones and Birth Outcomes - Ting Wu; Tao Li; Chen Zhang; Yan-Hui Hao; Si-Wei Zhang; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Biological Trace Element Research, 2025)

Synthetic microbial community maintains the functional stability of aerobic denitrification under environmental disturbances: Insight into the mechanism of interspecific division of labor - Yue He; Hui Yun; Liang Peng; Wenxue Wang; Ting Xu; Wenjie Zhang; Xiangkai Li (Water Research, 2025)

Unveiling the intricate dynamics of PM2.5 sulfate aerosols in the urban boundary layer: A pioneering two-year vertical profiling and machine learning-enhanced analysis in global Mega-City - Hongyi Li; Ting Yang; Yifan Song; Ping Tian; Jiancun He; Yining Tan; Yutong Tian; Yele Sun; Zifa Wang (Urban Climate, 2025)

Mitigation of methane emissions from urban sewer sediments: Sulfate addition and freeze-drying treatment - Lucheng Li; Lu Xu; Ting Xiao; Zanji He; Qijin Chen (Process Safety and Environmental Protection, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

A recycled polymetallic catalyst derived from acid mine drainage(AMD) for efficient tetracycline removal via peroxymonosulfate activation - Penghui Li; Ting Luo; Chunyao Gu; Peng He; Jianyu Zhu; Min Gan; Ke Zhang (Journal of Water Process Engineering, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Enhanced transformation of sulfadiazine by horseradish peroxidase activated persulfate progress: Characteristics, pathways, mechanisms, and ecotoxicities - Yifei Leng; Ying Zhang; Xiong Chen; Ting He; Fengyi Chang; Zhu Li; Yu Huang; Jun Wang; Wen Xiong (Journal of Environmental Chemical Engineering, 2025)

Global levels and variations of breast milk fatty acids and triacylglycerols: A systematic review and meta-analysis - Xinggang Ni; Zhiyi Zhang; Zeyuan Deng; Sufang Duan; Ignatius Man-Yau Szeto; Jian He; Ting Li; Jing Li (Food Chemistry, 2025)

Chemical constituents of Ainsliaea fragrans and their chemotaxonomic significance - Xiao-Ting He; Yun-Na Wang; Xue-Mei Zhou; Jing-Jing Zhang; Xiao-Li Li; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2025)

Light intensity is a crucial factor that regulates growth, physiological traits, antioxidant defense, and metabolite acquisition in Dendrobium denneanum - Hui Wang; Siyu He; Yijun Fan; Ting Li; Linlong Xu; Jie Ma; Junlan Wu; Haolin Liu; XuYang Liu; ChunHong Mou; Meng Zhao; Li Chen; et al. (Physiology and Molecular Biology of Plants, 2025)

Protein Kinase C Epsilon Overexpression Protects the Heart Against Doxorubicin-Induced Cardiotoxicity Via Activating SIRT1 - Danyong Liu; Chunyan Wang; Yao Chen; Xiaolei Huang; Yajie Wen; Shan Duan; Yin Cai; Xia Li; Jianfeng He; Kaijia Han; Ting Li; Yuantao Li; et al. (Cardiovascular Toxicology, 2025)
Doxorubicin (DOX)-induced cardiotoxicity (DIC) is known to be associated with reduction of cardiac protein kinase C epsilon (PKC-ε). PKC-ε promotes cell survival and protects hearts against various stresses. However, it is unclear whether or not the reduction in cardiac PKC-ε expression plays a causal role in DIC and in particular the potential underlying mechanism whereby PKC-ε may protect against DIC. C57BL/6 mice (8–10-week-old) were either treated with DOX administered intraperitoneally for a duration of 4 weeks to produce cardiotoxicity, or untreated in which mice received the same volume of saline. In vitro, neonatal rat ventricle cardiomyocytes were exposed to DOX for 24 h in the absence or presence of adenovirus overexpressing PKC-ε. Cardiomyocytes in a subgroup were treated with sirtuin-1 (SIRT1) selective inhibitor Ex527. Four weeks after DOX, cardiac contractile function was decreased concomitant with increased serum CK-MB and LDH levels as well as increases in Bax-to-Bcl-2 ratio and Cleaved Caspase 3 proteins expression, while PKC-ε and Sirt1 protein expressions were significantly decreased. In vitro, DOX reduced cardiomyocyte PKC-ε and SIRT1 protein expression, decreased cardiomyocyte viability, and increased LDH release with concomitant increases in oxidative stress and apoptosis. These changes were attenuated by overexpression of PKC-ε. IP study showed that PKC-ε could directly or indirectly bind SIRT1 in cardiomyocytes, and the protect effects of PKC-ε were further canceled by SIRT1 inhibition. In conclusion, activating SIRT1 may represent a major mechanism whereby PKC-ε protects the heart against DOX-induced cell apoptosis and oxidative stress. Graphical Abstract Dox induces cardiotoxicity via inhibiting PKC-epsilon/Sirt1 signaling which can be reversed by PKC-epsilon overexpression.

Capillary flow of hybrid mode for enhancement of flow rate on μTADs - Yixi Shi; Haonan Li; Hao Chen; Xionghui Li; Muyang Zhang; Qinghao He; Jie Zhou; Jiahua Zhong; Xinyi Chen; Huiru Zhang; Lok Ting Chu; Weijin Guo (Analytica Chimica Acta, 2025)

Long-term study of Citrus changshan-huyou Y.B. Chang essential oil: Chemical transformations and their impact on antibacterial efficacy - Wenbin Xiao; Jiajing Guo; Yanjiao Fu; Zixuan Li; Tongping Zhang; Mingwang He; Ting Liu; Yangbo Xiao; Xuebo Shang; Fuhua Fu; Gaoyang Li; Donglin Su; et al. (Food Chemistry, 2025)

Exposure-effect of PFOS and PFOA on lung function: An integrated approach with epidemiological, cellular, and animal studies - Jia-Xin Zhou; Xiao-Di Qin; Xuan Liu; Wan-Ting He; Mohammed Zeeshan; Shyamali C. Dharmage; Jennifer Perret; Dinh Bui; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Pore space optimization of hybrid ultramicroporous material for exceptional one-step C2H4 purification from C2H2/CO2/C2H4 mixture - Hong-Xiang Nie; Hong-Wei Chen; Ting Wang; Hongliang Huang; Qiang Gao; Mei-Hui Yu; Jian Zhu; Li-Bo Li; Zhenjie Zhang; Ze Chang; Xian-He Bu (Chemical Engineering Journal, 2025)

New perspectives on water chemistry classification of travertine/tufa - Qunwei Dai; Ting Zhang; Dejun An; Jingwen He; Jie Cui; Qiongfang Li; Ronglin Xu; Faqin Dong; Zheng Dang; Qianxi Song (Applied Geochemistry, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

A haplotype-resolved genome assembly of tetraploid Medicago sativa ssp. falcata - Wanying Li; Xuanzhao Li; Wei Li; Haibo Yang; Diandian Guo; Ting Guo; Yingying Meng; Qiang He; Hao Lin; Huilong Du; Lifang Niu (Science China Life Sciences, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Intelligent decoding platform for peptide sequences: SERS detection via high affinity self-assembled silver nanoparticles and machine learning analysis - Ting Zhang; Yingying He; Chengming Li; Huan Yao; Mingxu Zhang; Yang Li (Analytica Chimica Acta, 2025)

Replication factor C4, which is regulated by insulin-like growth factor 2 mRNA binding protein 2, enhances the radioresistance of breast cancer by promoting the stemness of tumor cells - Xiao-Yu Zhu; Pi-Song Li; Hui Qu; Xing Ai; Zi-Ting Zhao; Jia-Bei He (Human Cell, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Sulfurized anthracene as a new cathode material for highly reversible magnesium storage - Xi Chen; Sibylle Riedel; Sirshendu Dinda; Ting Wang; Fangfang He; Xiaojian Tu; Jinfeng Peng; Hans Joachim Räder; Björn Schmidt; Raiker Witter; Zhenyou Li; Maximilian Fichtner; et al. (Chemical Engineering Journal, 2025)

Lake level variability on the Northeastern Tibetan Plateau linked to interaction between Westerlies and Asian monsoon since the last deglaciation - Xueyun Ma; Zhifu Wei; Gen Wang; Ting Zhang; Pengyuan Zhang; Kaikang Liang; Zengguang Guo; Shangkun Li; Xiaomei Zhang; Jianzhen Chen; Zelong Li; Wei He; et al. (CATENA, 2025)

Codon Usage Bias: A Potential Factor Affecting VGLUT Developmental Expression and Protein Evolution - Yiran Zhao; Yu Zhang; Jiaxing Feng; Zixian He; Ting Li (Molecular Neurobiology, 2025)

The Systematic Analysis of the Impact of China Water Improvement and Fluoride Reduction Project on Children - Bo Yang; Feiqing Wang; Xu Yang; Jinyang Cheng; Juan Chen; Bingbing Li; Ying Zhou; Xiaoxu Chen; Bo Wei; Xiaoshuang Yuan; Ting Tian; Dongxin Tang; et al. (Biological Trace Element Research, 2025)

Preparation of wood formaldehyde-free adhesive by concentrated water delignification black liquor - Ting Zhang; Jianli Tan; Yongqi Li; Yexuan Tang; Yan He; Yuanyuan Ge; Xuemin Cui (Journal of Cleaner Production, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Solid phase extraction-surface enhanced Raman spectroscopy (SPE-SERS) test of antibiotic residues in Milk based on au@ MIL-101 NPs - Mengyue Gao; Qiao Chen; ZhiHao Li; YiFang Zhan; LiHua Wang; Ting He; Qi Yao; Fengmei Jin; Jiming Hu (Food Chemistry, 2025)

Enhancing the formation of functional glucosinolate degradation products in fermented broccoli stalk by-product with lactic acid bacteria - Qinghang Wu; Daqun Liu; Jianming Zhang; Ting Li; Haiyue Niu; Xiaoting Xin; Shengming Zhao; Chengyun He; Chengcheng Zhang (Food Chemistry, 2025)

Influence of the main controlling factors on the tangential restitution coefficient of rockfall impact - Zhong-Min Ji; Ting-Hui Wang; Jie Wu; Fa-Quan Wu; Zhen-Hua Li; Dong-Po Wang; Yi-Ju Tang; Chang-Le Zhao; Qing-He Niu (Engineering Geology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Involvement of copper in cell death and cancer - Jiahao Xie; Yue Su; Wenzhong Shang; Yanfang Wu; Junjia He; Ting Li; Yeyu Shen; Youni Zhang; Xiangmin Tong; Qiong Bian (Apoptosis, 2025)

Effects of Enterocytozoon hepatopenaei infection on intestinal immune defense and physiological processes of Penaeus vannamei - Zheng Cao; Chuanyu He; Zhipeng Yin; Caiyi Chen; Fan Li; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Frontiers in Marine Science, 2025)
As the main pathogen causing growth retardation, EHP is considered to be mainly parasitic in the hepatopancreas of shrimp. However, the intestines of shrimp infected with EHP frequently exhibit syndromes such as jejunum and white midgut. Therefore, the challenge experiment was carried out in this study to compare the differences in intestinal histology, digestion and absorption, immune defense and oxidative stress of P. vannamei between the control group and EHP infection group. Histological analysis showed that EHP infection significantly damaged the intestine of the shrimp, including intestinal villus rupture and outer membrane impairment. Concurrently, EHP infection can trigger intestinal immune response, and the expression of key immune genes like Toll, myeloid differentiation factor, anti-lipopolysaccharide factor, and Relish was significantly enhanced, while the expression of IMD and alkaline phosphatase was suppressed. Additionally, antioxidant genes manganese superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, and nuclear factor E2-related factor 2 were up-regulated to varying extents in EHP infection group, and the contents of lipid peroxides and malondialdehyde were heavily accumulated. Moreover, the expression levels of key genes involved in nutrient absorption, transport and synthesis, such as glucose transporter 1, Na + -K + ATPase, fatty acid synthase, acetyl-CoA carboxylase, rapamycin kinase, mTOR regulation-related protein, eukaryotic translation initiation factor 4E binding protein, ribosomal protein S6 kinase, were significantly up-regulated. However, the activities of amylase, lipase, and trypsin were inhibited in EHP infection group throughout the experiment. In summary, EHP infection damaged the intestine of P. vannamei , accompanied by immune response and oxidative stress. At the same time, nutrient transport and synthesis pathways were activated, while digestive enzyme activities were inhibited, indicating that in order to maintain survival, shrimps must accelerate material transport. Unfortunately, it remains in a state of nutrient deficiency that ultimately affects growth.

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Observation, distribution, and characteristics of microplastics in sediments from the estuary and river network areas of Pearl River Delta, China - Haijun He; Ting Yu; Xueli Chen; Yujie Yang; Feng Li; Huayang Gan (Regional Studies in Marine Science, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

On-demand removable hydrogel film derived from gallic acid-phycocyanin and polyvinyl alcohol for fruit preservation - Wei Gong; Ting-qi Yang; Wan-ying He; Yu-xin Li; Jiang-ning Hu (Food Chemistry, 2025)

Engineered food-derived hesperetin as heterojunction photosensitizer for inhibiting Staphylococcus aureus and degrading patulin, and its application in perishable strawberries - Ting Du; Jiazhen Wang; Zhenqing Guo; Yu He; Shaochi Wang; Xiang Li; Nannan Qiu; Jianlong Wang; Wentao Zhang (Food Chemistry, 2025)

Microfluidic fabrication of lipid nanoparticles for co-delivery of siRNA and hydroxychloroquine: An engineered theranostic platform for enhanced breast cancer treatment - Lu Huang; Wenli Guo; Ting Zhao; Yanru Feng; Yue Li; Qingqing An; Chenxi Li; Yiwei Tian; Huaxing Zhang; Chenming Zhou; Yanan Sun; Chaoxing He; et al. (Chemical Engineering Journal, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Interactive effects of microplastics and cadmium on soil properties, microbial communities and bok choy growth - Mengxiao Li; Jiaju He; Xiaofeng Chen; Xiaoman Dong; Shuang Liu; Christopher W.N. Anderson; Minghua Zhou; Xuesong Gao; Xiaoyan Tang; Di Zhao; Ting Lan (Science of The Total Environment, 2024)

Urine is better for rare earth elements bimonitoring in long-term exposed population: An exposure-response relationship study - Zhizhou He; Li Liu; Ting Wang; Cailan Zhou; Xuewei Zhang; Nan Wu; Mengmeng Xu; Jianqiong Gao; Bin Li; Yonglan Wang; Qiang Zhi; Chenguang Zhang; et al. (Environmental Research, 2024)

Riparian restoration in sandy zones with alfalfa as pioneer plant in initial stage of soil and water bioengineering - Lin Yang; Lina Cao; Ting Cao; Hongyong Xiang; Chunguang He; Jia Li; Xiaoyue Zhang; Sayramgul Abu Dumusa; Yu Leng (Ecological Engineering, 2024)

An aptamer-integrated conductive microneedle biosensor for real-time transdermal cortisol monitoring - Li Yue Jing; Yangkai Fan; Bo Zhi Chen; Dehui Li; Yu Ting He; Guo Liang Zhang; Ling Liang; Jie Du; Yuan Wang; Xin Dong Guo (Chemical Engineering Journal, 2024)

Enhanced ethanol synthesis via CO2 hydrogenation using La-Doped CuFeOx catalysts - Kailong He; Yetong Li; Zhenbo Li; Jie Chen; Li Tan; Ting Qiu; XinGang Li; Xiaoxun Ma; Chengyi Dai (Chemical Engineering Journal, 2024)

A Contrastive-Learning-Based Deep Neural Network for Cancer Subtyping by Integrating Multi-Omics Data - Hua Chai; Weizhen Deng; Junyu Wei; Ting Guan; Minfan He; Yong Liang; Le Li (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Hg-mining-induced soil pollution by potentially toxic metal(loid)s presents a potential environmental risk and threat to human health: A global meta-analysis - Li Chen; Xiaosan Luo; Haoran He; Ting Duan; Ying Zhou; Lequn Yang; Yi Zeng; Hansong Chen; Linchuan Fang (Soil Ecology Letters, 2024)

Prevalence of Tick Infection with Bartonella in China: A Review and Meta-analysis - Yuhua Wang; Ruishan Li; Ting Yin; Zhen He; Zhenhua Lu; Zhongjun Shao; Yong Long (Acta Parasitologica, 2024)

Log Facies Identification via Dynamic Classifier Selection - Mei He; Shu-wen Guo; Ting He; Hao Li; Chun-xiang Guo; Yu Zhong; Fang-fang Wang (Applied Geophysics, 2024)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Metabolomics reveals the potential mechanism of La(III) promoting enrichment of Sodium hydrogen arsenate and Roxarsone in Solanum nigrum L. - Yining Zhu; Ruijie Che; Zhongtian Dong; Ting Guo; Xin He; Jining Li; Fenghe Wang (Science of The Total Environment, 2024)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

Ensuring China's food security in a geographical shift of its grain production: Driving factors, threats, and solutions - Shi Xue; Zhou Fang; Carena van Riper; Wei He; Xuxia Li; Fan Zhang; Ting Wang; Changgao Cheng; Qin Zhou; Zhongde Huang; Yang Bai (Resources, Conservation and Recycling, 2024)

Investigating the role of membrane lipid composition differences on spray drying survival in Lactobacillus bulgaricus using non-targeted Lipidomics - Fengzhi Qiao; Shaolei Wang; Jian He; Weilian Hung; Xia Ma; Pimin Gong; Jiadong Li; Ting Sun; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Removal of antibiotics from aquaculture wastewater using a continuous flow/EC/PMS coupled system - Lulu Long; Jingrong Li; Ting Hou; Min Liu; Yuhuan Lin; Xingwei Zhu; Chao Chen; Gang Yang; Jingsong He (Chemical Engineering Journal, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

High-resolution comprehensive regional development mapping using multisource geographic data - Linxin Li; Ting Hu; Guangyi Yang; Wei He; Hongyan Zhang (Sustainable Cities and Society, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

PML_30: A high resolution (30 m) estimates of evapotranspiration based on remote sensing model with application in an arid region - Ting Liang; Changming Li; Yufen He; Jing Tan; Wenqian Niu; Yaokui Cui; Hanbo Yang (Journal of Hydrology, 2024)

Nitrogen removal performance and functional microbial communities evolution in a continuous up-flow fixed bed anammox system - Zheng Lu; Junting Zhao; Zhenjun Wu; Ting Guo; Menghan Wang; Xiaomin Li; Dongjin Wan; Zhimin Du; Qiaochong He (Journal of Environmental Chemical Engineering, 2024)

A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

One undescribed glycoside benzofuran derivative and a new p -hydroxybenzoate glycoside from the leaves of Illicium dunnianum Tutcher - Xiao-qing He; Hai-bo Li; Ting Li; Xin-yin Chen; Zhen-zhong Wang; Xin-sheng Yao; Wei Xiao; Yang Yu (Natural Product Research, 2024)

Synergistic promotion of antimony transformation in the interaction of Acidithiobacillus ferrooxidans and pyrite by driving the formation of reactive oxygen species and secondary minerals - Peng He; Quanliu Yang; Chunyao Gu; Mengfei Liu; Penghui Li; Ting Luo; Jiancheng Chen; Junwen Chen; Jianyu Zhu; Min Gan (Chemosphere, 2024)

Nitrogenous fertilizer plays a more important role than cultivars in shaping sorghum-associated microbiomes - Fangfang Li; Anqi Sun; Xiaoyan Jiao; Dan-Ting Yu; Peixin Ren; Bing-Xue Wu; Peng He; Li Bi; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2024)

Preparation of gelatin-starch shell-yolk microspheres by water-in-water emulsion method: Effects of starch crystal type and cross-linking - Zhirenyong Zhang; Xiaoxue He; Ting Yan; Yuyu He; Chaoxi Zeng; Shiyin Guo; Qingming Li; Huiping Xia (Food Hydrocolloids, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Identification and characterization of a novel type II toxin-antitoxin system in Aeromonas veronii - Caihong Ji; Ting He; Binbin Wu; Xiaomei Cao; Xiaping Fan; Xia Liu; Xiaodan Li; Miao Yang; Jihan Wang; Ling Xu; Shengbiao Hu; Liqiu Xia; et al. (Archives of Microbiology, 2024)

Metaphire guillelmi exhibited predominant capacity of arsenic efflux - Xiayun Zang; Mingyue He; Yuanzhou Xu; Ting Che; Fei Wang; Jingjing Xu; Huijuan Zhang; Feng Hu; Li Xu (Chemosphere, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Universal materials model of deep-learning density functional theory Hamiltonian - Yuxiang Wang; Yang Li; Zechen Tang; He Li; Zilong Yuan; Honggeng Tao; Nianlong Zou; Ting Bao; Xinghao Liang; Zezhou Chen; Shanghua Xu; Ce Bian; et al. (Science Bulletin, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Bio-inspired gradient poly(lactic acid) nanofibers for active capturing of PM0.3 and real-time respiratory monitoring - Guiying Zhu; Cunmin Wang; Ting Yang; Na Gao; Yifan Zhang; Jintuo Zhu; Xinjian He; Jiang Shao; Shihang Li; Mingming Zhang; Shenghui Zhang; Jiefeng Gao; et al. (Journal of Hazardous Materials, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

Elucidating the role of polar functional groups in fluorinated polymer artificial interphase for stable lithium anodes - Kun Li; Zhen Wang; Borui Yang; Ting Li; Bin Li; Jiahao Chen; Zhongfu Yan; Miao He; Anjun Hu; Jianping Long (Chemical Engineering Journal, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Elucidate the molecular basis of ampholytic chitosan as a high-performance cryoprotectant to myosin denaturation: The importance of saccharide charges - Ting Zhang; Yongxin Teng; Yaluan He; Yonghui Li; Yue Yuan; Bin Li; Yijie Chen; Xiangwei Zhu (Food Hydrocolloids, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Rare earth elements applied to phytoremediation: Enhanced endocytosis promotes remediation of antimony contamination with different valence levels in Solanum nigrum L. - Ding He; Ting Guo; Zhongtian Dong; Jining Li; Fenghe Wang (Science of The Total Environment, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

Two-way predation between larvae of Spodoptera frugiperda and Spodoptera litura - Yuxue Wang; Natasha Isabel Tanatsiwa Mbiza; Yonghao Yu; Haoran Zhang; Zongwei Hu; Ting Liu; Yi Wang; Yi Zhang; Xincheng Luo; Longyan Chu; Yazhen Yang; Xiangping Wang; et al. (Journal of Asia-Pacific Entomology, 2024)

CoNi alloy nanoparticles confined by N-doped carbon matrix with tailored d-Band center for electrocatalytic hydrogen evolution - Ting Zhang; Zhen He; Li Yin; Wei Gao; Yuxin Wang (Fuel, 2024)

Petrophysical characterization of coal subjected to cyclic N-methylpyrrolidone treatment based on two-dimensional NMR T1-T2 - He Li; Qingyi Guo; Meng Liu; Jiexin Lu; Yidu Hong; Ting Liu; Zheng Wang (Fuel, 2024)

Emulsion stability enhancement against storage and environment stresses using complex plant protein and betanin - Qin Geng; Ting Hu; Jun Chen; Changhong Li; Ti Li; Xuemei He; Jialong Han; Chengmei Liu; Taotao Dai (Food Bioscience, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Metagenomic and transcriptomic analysis revealing the impact of oxytetracycline and ciprofloxacin on gut microbiota and gene expression in the Chinese giant salamander (Andrias davidianus) - Ting Ye; Shumao He; Jiahui Li; Jianlin Luo; Sixue Yang; Peng Wang; Can Li (Aquatic Toxicology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Popcorn-like bimetallic palladium/platinum exhibiting enhanced peroxidase-like activity for signal enhancement in lateral flow immunoassay - Qianqian Cao; Yiqin Liu; Lin Yang; Ting Tan; Jian He; Weiwei Chen; Ranhui Li; Weiguo Wang (Analytica Chimica Acta, 2024)

Photobiomodulation therapy moderates cancer cachexia-associated muscle wasting through activating PI3K/AKT/FoxO3a pathway - Yonghua Li; Yibing Chen; Yuan Liao; Ting Huang; Qing Tang; Chengsi He; Liu Xu; Haocai Chang; Hongsheng Li; Quentin Liu; Dongming Lai; Qing Xia; et al. (Apoptosis, 2024)

Industry chain and challenges of microalgal food industry-a review - Yuanhao Chen; Honghao Liang; Hong Du; Valentina Jesumani; Weiling He; Kit-Leong Cheong; Tangcheng Li; Ting Hong (Critical Reviews in Food Science and Nutrition, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Four new compounds from fruits of Hypericum patulum Thunb. - Li Jiang; Xue Ma; Yang Wang; Jingyi Xue; Zhilong He; Yushan Nie; Ting Liu; Yong-Lin Wang; Yongjun Li (Natural Product Research, 2024)

Selective breeding in the noble scallop (Chlamys nobilis) for low-temperature resistance to reduce overwintering losses - Chuanxu Zhang; Cheng He; Yizhou Sun; Hongkuan Zhang; Ting Ye; Faxin Liu; Hongyu Ma; Shengkang Li; Huaiping Zheng (Aquaculture, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Lemon essential oil nanoemulsions: Potential natural inhibitors against Escherichia coli - Wenbin Xiao; Zhipeng Gao; Ting Liu; Weiming Zhong; Sifan Jiang; Mingwang He; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Microbiology, 2024)

The influence of in situ purification system on pathogen in the river fed by the drainage of sewage plant - Zhao-xu Peng; Yu He; Lu-ji Yu; Zi-yao Hao; Ting-mei Li; Li-kun Gu; Li Wang (Environmental Science and Pollution Research, 2024)

Tough, self-healing and injectable dynamic nanocomposite hydrogel based on gelatin and sodium alginate - Li Ting Gao; Yong Mei Chen; Yasir Aziz; Wei Wei; Xin Yi Zhao; Yuan He; Jianhui Li; Haopeng Li; Hideyuki Miyatake; Yoshihiro Ito (Carbohydrate Polymers, 2024)

Stem Cell-Based Strategies: The Future Direction of Bioartificial Liver Development - Lei Feng; Yi Wang; Yu Fu; Ting Li; Guolin He (Stem Cell Reviews and Reports, 2024)

Quantitative Trait Locus Mapping Combined with RNA Sequencing Reveals Candidate Genes for Chlorophyll Content in Oilseed Rape Leaves - Li Yuanhong; Cai Lei; He Yuqi; Ding Ting; Tian Entang; Zhang Jiefu; Yu Kunjiang; Chen Zhuo; Wang Xiaodong (Journal of Plant Growth Regulation, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Transcriptomics combined with physiological analysis provided new insights into the Zn enrichment capacity and tolerance mechanism of Dendrobium denneanum Kerr - Yuanyuan Liu; Erya Xu; Yijun Fan; Linlong Xu; Jie Ma; Xuebing Li; Hui Wang; Siyu He; Ting Li; Yujiao Qin; Jingtao Xiao; Aoxue Luo (Plant Science, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Effect of Resveratrol on physicochemical structure evolution of lignite during spontaneous combustion - Xianhua Shen; He Li; Jiexin Lu; Yi Lu; Meng Liu; Baiquan Lin; Wei Yang; Yidu Hong; Ting Liu; Zheng Wang (Fuel, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Mechanisms of Ferritinophagy and Ferroptosis in Diseases - Siqi Li; Ping Huang; Feifan Lai; Ting Zhang; Jiaqi Guan; Haitong Wan; Yu He (Molecular Neurobiology, 2024)

Prediction of state transitions in 3D core dynamics and xenon transients based on dynamic mode decomposition - Wenhuai Li; Sitao Peng; Jinggang Li; Qingyun He; Tao Wang; Yijun Zhang; Haoliang Lu; Ting Wang; Peng Ding (Annals of Nuclear Energy, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Lanthanum promotes Solanum nigrum L. growth and phytoremediation of cadmium and lead through endocytosis: Physiological and biochemical response, heavy metal uptake and visualization - Ting Guo; Ding He; Yongqiang Liu; Jining Li; Fenghe Wang (Science of The Total Environment, 2024)

Urbanization and weather dynamics co-dominated the spatial-temporal variation in pCO2 and CO2 fluxes in small montanic rivers draining diverse landscapes - Zhaoyin Qing; Xiaofeng Wang; Xianxiang Li; Chen Jian; Yi Yang; Ting Zhou; Tingting Liu; Shuangshuang Liu; Yafang Huang; Yixin He (Journal of Environmental Management, 2024)

Degradation on BDE209 in the soil by kaolin-supported sulfurized nano-zero-valent iron activated persulfate system: Insights mechanism and DFT calculations - Fang Zhu; Huijie Lu; Ting Li; Siying He; Huishen Xu (Journal of Environmental Chemical Engineering, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Complete decomposition of poly(ethylene terephthalate) by crude PET hydrolytic enzyme produced in Pichia pastoris - Chun-Chi Chen; Xian Li; Jian Min; Ziyin Zeng; Zhiyuan Ning; Hailin He; Xin Long; Du Niu; Rouming Peng; Xin Liu; Yu Yang; Jian-Wen Huang; et al. (Chemical Engineering Journal, 2024)

Activated carbon-boosted BiOI in CO2 adsorption and electron transfer for photothermally catalyzed CO2 oxidative dehydrogenation of propane - Run-Qing Miao; Zhen-Hong He; Bao-Ting Wu; Jiajie Liu; Sen-Wang Wang; Kuan Wang; Weitao Wang; Lu Li; Zhao-Tie Liu (Chemical Engineering Journal, 2024)

RETRACTED ARTICLE: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2024)

Accurate Shortwave Radiation Simulation with a Two-Layer Aerosol Model in Xinjiang Region - Guan Huang; Yonghang Chen; Qiong Liu; Pengtao Wang; Qianshan He; Qing He; Shuai Li; Weiling Shao; Ting Fan (Journal of Meteorological Research, 2024)

Quantitative SARS-CoV-2 exposure assessment for workers in wastewater treatment plants using Monte-Carlo simulation - Cheng Yan; Yi-ning Hu; Zi-cheng Gui; Tian-nuo Lai; Wajid Ali; Nian-hong Wan; Shan-shan He; Sai Liu; Xiang Li; Ting-xu Jin; Zaheer Ahmad Nasir; Sonia Garcia Alcega; et al. (Water Research, 2024)

Foliar spraying of lanthanum activates endocytosis in lettuce (Lactuca sativa L.) root cells, increasing Cd and Pb accumulation and their bioaccessibility - Xinyan Zong; Yongqiang Liu; Xinying Lin; Ding He; Zhongtian Dong; Ting Guo; Jining Li; Hongbo Li; Fenghe Wang (Science of The Total Environment, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Exploring the effect of photobiomodulation and gamma visual stimulation induced by 808 nm and visible LED in Alzheimer's disease mouse model - Hao Xu; Ziyi Luo; Renlong Zhang; Iuliia Golovynska; Yanxia Huang; Soham Samanta; Ting Zhou; Shaowei Li; Bingang Guo; Liwei Liu; Xiaoyu Weng; Jun He; et al. (Journal of Photochemistry and Photobiology B: Biology, 2024)

MicroRNA-217-5p triggers dopaminergic neuronal degeneration via autophagy activation under Atrazine exposure - Bingyun Li; Yujia Jiang; Ting Wang; Weiwei Liu; Xiaojuan Chen; Jinyi He; Zeyu Du; Ruijiao Yang; Danxiu Miao; Yanshu Li (Environmental Pollution, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Efficiently Removal of Tetracycline from Water by Fe3O4-sludge Biochar - Liyang Zhao; Peixi He; Qian Li; Honghui Pan; Ting Xie; Shiyong Huang; Shaohua Cao; Xixiang Liu (Water, Air, & Soil Pollution, 2024)

Estimating the complete in-situ stress tensor along deep tunnels with frequent rockbursts near a steep valley - Ben-Guo He; Hong-Pu Li; Xia-Ting Feng; Xiang-Rui Meng (Bulletin of Engineering Geology and the Environment, 2024)

Transcriptome analysis of Iris japonica var. variegata for chlorophyll and photosynthesis-related pathways involved in white–green striped leaves - Xiaofang Yu; Linjie Yue; Qingling He; Shurui Li; Yunhao Zheng; Zhiwen Wang; Heting Wang; Rouzhi Liu; Xin Huang; Xue Xiao; Lijuan Yang; Ting Lei (Acta Physiologiae Plantarum, 2024)

Long‐term warming increased carbon sequestration capacity in a humid subtropical forest - Xujun Liu; Zhiyang Lie; Peter B. Reich; Guoyi Zhou; Junhua Yan; Wenjuan Huang; Yingping Wang; Josep Peñuelas; David T. Tissue; Mengdi Zhao; Ting Wu; Donghai Wu; et al. (Global Change Biology, 2024)
Tropical and subtropical forests play a crucial role in global carbon (C) pools, and their responses to warming can significantly impact C‐climate feedback and predictions of future global warming. Despite earth system models projecting reductions in land C storage with warming, the magnitude of this response varies greatly between models, particularly in tropical and subtropical regions. Here, we conducted a field ecosystem‐level warming experiment in a subtropical forest in southern China, by translocating mesocosms (ecosystem composed of soils and plants) across 600 m elevation gradients with temperature gradients of 2.1°C (moderate warming), to explore the response of ecosystem C dynamics of the subtropical forest to continuous 6‐year warming. Compared with the control, the ecosystem C stock decreased by 3.8% under the first year of 2.1°C warming; but increased by 13.4% by the sixth year of 2.1°C warming. The increased ecosystem C stock by the sixth year of warming was mainly attributed to a combination of sustained increased plant C stock due to the maintenance of a high plant growth rate and unchanged soil C stock. The unchanged soil C stock was driven by compensating and offsetting thermal adaptation of soil microorganisms (unresponsive soil respiration and enzyme activity, and more stable microbial community), increased plant C input, and inhibitory C loss (decreased C leaching and inhibited temperature sensitivity of soil respiration) from soil drying. These results suggest that the humid subtropical forest C pool would not necessarily diminish consistently under future long‐term warming. We highlight that differential and asynchronous responses of plant and soil C processes over relatively long‐term periods should be considered when predicting the effects of climate warming on ecosystem C dynamics of subtropical forests.

The dual effect of disodium anthraquinone-2,6-disulfonate (AQDS) on the Cr(VI) removal by biochar: The enhanced electron transfer and the inhibited adsorption - Xue Wang; Peng Zhang; Meixuan Wu; Ting He; Can Li; Lijuan Liu; Shunling Li; Zhaofeng Chang; Di Lang; Wei Du; Hao Li; Bo Pan (Chemosphere, 2023)

Intraspecific variations of leaf hydraulic, economic, and anatomical traits in Cinnamomum camphora along an urban-rural gradient - Cheng Zhang; Nuo Huang; Fengyu Zhang; Ting Wu; Xianjin He; Jianan Wang; Yiyong Li (Science of The Total Environment, 2023)

Cultivation and biogeochemical analyses reveal insights into biomineralization caused by piezotolerant iron-reducing bacteria from petroleum reservoirs and their application in MEOR - Hao Dong; Li Yu; Ting Xu; Yulong Liu; Jian Fu; Yanlong He; Ji Gao; Jiaqi Wang; Shanshan Sun; Yuehui She; Fan Zhang (Science of The Total Environment, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

Failure Modes of Jointed Granite Subjected to Weak Dynamic Disturbance Under True-Triaxial Compression - Ben-Guo He; Lei Wang; Xia-Ting Feng; Rong-Li Zhen (Rock Mechanics and Rock Engineering, 2023)

Insufficient SIRT1 in macrophages promotes oxidative stress and inflammation during scarring - Ting He; Xiaozhi Bai; Yan Li; Dongliang Zhang; Zhigang Xu; Xuekang Yang; Dahai Hu; Juntao Han (Journal of Molecular Medicine, 2023)

Breaking the salty spell: Understanding action mechanism of melatonin and beneficial microbes as nature's solution for mitigating salt stress in soybean - Zhenyu Fan; Feifei He; Ting Wu; Bowen Li; Jin Xiao; Zhigang Wang (South African Journal of Botany, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Labdane and ent-halimane diterpenoids with STAT3-inhibitory activity from Leonurus sibiricus - Chen Wang; Jiao Tian; Chaoge Liu; Yiming He; Jiahang Li; Qiang Zhang; Ting Xiao; Chunfeng Xie; Cheng Yang (Phytochemistry, 2023)

Asymmetry of blue and green water changes in the Yangtze river basin, China, examined by multi-water-variable calibrated SWAT model - Ning Nie; Ting Li; Yiyi Miao; Wanchang Zhang; Huiran Gao; Hongming He; Dengzhong Zhao; Min Liu (Journal of Hydrology, 2023)

Quantifying ant diversity and community in a subalpine forest mosaic: a comparison of two methods - Chuan-Jing Zhang; Yi-Ting Cheng; Xian-Shu Luo; Yao Chen; Yu-Chao He; Yan-Pang Li; Zhi-Pang Huang; Matthew B. Scott; Wen Xiao (Journal of Insect Conservation, 2023)
Sampling efficiency, composition and detection biases associated with pitfall-trap and sample plot (standardised hand-collecting) methods were compared at seven high montane sites at Lasha Mountain, Yunnan, China. Rarefaction-interpolation curves showed total species diversity and sample coverage from each method were undifferentiated. Permutational multivariate analysis of variance showed highly overlapping communities. However, of all species collected, just 53% of all species found were shared between the two methods; 30% were exclusive to sample plot samples and 17% were exclusive to pitfall traps. Modelled comparisons of species richness (alpha) and proportion of species from the population (beta diversity) showed differences between methods. Permutational multivariate analysis of variance blocked by site showed community composition differed between methods, defined largely by the presence of a few dominant species. Implications for insect conservation : Our findings suggest that results from the two methods cannot be directly compared and are imperfect substitutes to one another. For long-term monitoring of biodiversity in complex forest mosaic systems, we suggest integrating a suite of complementary methods to achieve more complete representation of ant composition and diversity.

Drought shifts soil nematodes to smaller size across biological scales - Leilei Lu; Gen Li; Nianpeng He; Huixin Li; Ting Liu; Xianping Li; Joann K. Whalen; Stefan Geisen; Manqiang Liu (Soil Biology and Biochemistry, 2023)

Effective mechanisms in the formation of pool-rimstone dams in continental carbonate systems: The case study of Huanglong, China - Ting Zhang; Qunwei Dai; Dejun An; R. Agustin Mors; Qiongfang Li; Ricardo A. Astini; Jingwen He; Jie Cui; Ruiyang Jiang; Faqin Dong; Zheng Dang (Sedimentary Geology, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Identification of suitable tributaries to compensate fish habitat loss in dammed rivers using environmental DNA metabarcoding - Yuqing Lin; Tao Feng; Lei Tang; Hui Zhang; Jianyun Zhang; Qiuwen Chen; Shufeng He; Ting Li (Hydrobiologia, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

4-hydroxylonchocarpin and corylifol A: The potential hepatotoxic components of Psoralea corylifolia L - Linqi Ouyang; Zhiqiang Fan; Yang He; Long Tan; Guoyan Deng; Qin He; Yiran He; Ting Ouyang; Congjie Li; Qin Zhang; Hongyu Liu; Yajie Zuo (Toxicology Letters, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Gross nitrogen transformations and ammonia oxidizers affected by nitrification inhibitors and/or organic amendments in a calcareous soil: A 15N tracing study - Xiaoqian He; Mengxiao Li; Minghua Zhou; Wei Zhou; Guangdeng Chen; Yanyan Zhang; Yang Li; Min Zeng; Xuesong Gao; Ting Lan (Applied Soil Ecology, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Advanced oxidation-based combined conditioning technologies to improve sludge dewaterability: A mini review - Zhongqi He; Xu Zhou; Xiumin Fan; Wenbiao Jin; Chuan Chen; Bowen Yan; Shiyu Yin; Ting Zhou; Xuan Li; Guangming Jiang (Journal of Water Process Engineering, 2023)

Chickpea protein hydrolysate as a novel plant-based cryoprotectant in frozen surimi: Insights into protein structure integrity and gelling behaviors - Chao Wang; Junhui Rao; Xueyin Li; Diheng He; Ting Zhang; Jianteng Xu; Xi Chen; Lan Wang; Yue Yuan; Xiangwei Zhu (Food Research International, 2023)

Long-term drying trends since the mid-Holocene in the Qaidam Basin - Ting Zhang; Gen Wang; Yongli Wang; Zhifu Wei; Wei He; Xueyun Ma; He Ma; Xiaoli Yu; Pengyuan Zhang; Shangkun Li; Jingyi Wei; Lun Li (CATENA, 2023)

The catalytic oxidation process of atrazine by ozone microbubbles: Bubble formation, ozone mass transfer and hydroxyl radical generation - Ting Liu; Bin Zhang; Wenqian Li; Boda Li; Ziwen Han; Yanjie Zhang; An Ding; Shutao Wang; Jun Ma; Xu He (Chemosphere, 2023)

Development and application of a rapid screening and quantification method for multi-class herbicide residues in fishery products using UPLC-Q-Tof-MS/MS: Evidence for prometryn residues in shellfish - Jie Peng; Jinhua Gan; Ting Liu; Xiaoqian Ju; Jianwu Chen; Li He (Food Control, 2023)

Impact history and origin of lunar meteorite Northwest Africa 15528 - Runchuan Liu; Huaiyu He; Thomas Smith; Hanqing Ye; Huapei Wang; Xuhang Zhang; Fei Su; Ziheng Liu; Wei Guo; Peng Yang; Chuantong Zhang; Dingshuai Xue; et al. (Science China Earth Sciences, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Watershed urbanization dominated the spatiotemporal pattern of riverine methane emissions: Evidence from montanic streams that drain different landscapes in Southwest China - Xianxiang Li; Yixin He; Xiaofeng Wang; Huai Chen; Tingting Liu; Yizi Que; Xingzhong Yuan; Shengnan Wu; Ting Zhou (Science of The Total Environment, 2023)

Enhanced photo-electro-Fenton degradation performance using graphene structure-oriented MOFs (2Fe/Co)/CNF cathode membrane - Bingzhang Li; Yao Meng; Xiaoxia Lin; Degui Tu; Shunxi Shen; Ting He; Yuqi Li; Hui Zhang (Journal of Cleaner Production, 2023)

Foliar application of lanthanum promotes growth and phytoremediation potential Solanum nigrum L - Ding He; Ting Guo; Chunqing Peng; Jining Li; Fenghe Wang (Journal of Environmental Management, 2023)

Quantifying the effects of submicroscopic metallic iron on VIS–NIR spectra of lunar soils - Yanhua Peng; Siting Zhang; Hong Tang; Zhuang Guo; Wen Yu; Guozhu Chen; Chen Li; Bingkui Miao; Bing Mo; Encheng He; Ting Zhou; Zhipeng Xia; et al. (Icarus, 2023)

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Non-covalent interaction of complex plant protein and betanin: Mechanism of improving thermal stability of betanin - Ting Hu; Taotao Dai; Xuemei He; Lizhen Deng; Ti Li; Jian Sun; Chengmei Liu; Jun Chen (Food Hydrocolloids, 2023)

The importance of moisture in regulating soil organic carbon content based on a comparison of “enzymic latch” and “iron gate” in Zoige Plateau peatland - Ruixuan Li; Hanqing Luo; Jianlan Yu; Ling Luo; Yan He; Shihuai Deng; Ouping Deng; Dezhi Shi; Jinsong He; Hong Xiao; Lilin Wang; Ting Lan (CATENA, 2023)

Links between geochemical weathering on the NE Tibetan Plateau and global climate change since the Last Deglacial - Xueyun Ma; Zhifu Wei; Yongli Wang; Gen Wang; Ting Zhang; Wei He; Xiaoli Yu; He Ma; Pengyuan Zhang; Shangkun Li; Qiaohui Fan (CATENA, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Optimize lettuce washing methods to reduce the risk of microplastics ingestion: The evidence from microplastics residues on the surface of lettuce leaves and in the lettuce washing wastewater - Ding He; Ting Guo; Jining Li; Fenghe Wang (Science of The Total Environment, 2023)

Calcium isotopic geochemistry of geothermal systems in the tectonically active southeastern Tibetan Plateau - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; Jun Zhong; Ting-Ting Ma; Jian Sun; Wen-Yan He; Cong-Qiang Liu (Science of The Total Environment, 2023)

Structural variation (SV)-based pan-genome and GWAS reveal the impacts of SVs on the speciation and diversification of allotetraploid cottons - Shangkun Jin; Zegang Han; Yan Hu; Zhanfeng Si; Fan Dai; Lu He; Yu Cheng; Yiqian Li; Ting Zhao; Lei Fang; Tianzhen Zhang (Molecular Plant, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Depositional processes of the mixed siliciclastic-carbonate system in the Lower Cambrian Xiannüdong Formation in the northern Sichuan Basin, South China - Ting Li; Weiqiang Yang; Chaojin Lu; Pingping Li; Zhehang Xu; Yuan He; Jinbao Duan; Huayao Zou (Marine and Petroleum Geology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Brittle failure modes of underground powerhouses: an insight based on true triaxial compression tests - Ben-Guo He; Qiang Tong; Xia-Ting Feng; Qiang Jiang; Hui Li; Yonghong Li; Zhiguo Li (Bulletin of Engineering Geology and the Environment, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Identification of a new benzophenanthridine alkaloid from Eomecon chionantha induced necroptosis in breast cancer cells - Peng Yang; Ya-ting Cheng; Xin Huang; Bin Huang; Li Yi; Hai-lang He; Yang Xie (Natural Product Research, 2023)

Predatory protists play predominant roles in suppressing soil-borne fungal pathogens under organic fertilization regimes - Peixin Ren; Anqi Sun; Xiaoyan Jiao; Ju-Pei Shen; Dan-Ting Yu; Fangfang Li; Bingxue Wu; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2023)

DEGENERATED LEMMA (DEL) regulates lemma development and affects rice grain yield - You Jing; Chen Wenbo; He Zhifeng; Xiang Yan; Zhang XinFang; Wei Mi; Wu RuHui; Shen Wenqiang; Zhang Jun; Duan QianNan; He Guanghua; Li Yunfeng; et al. (Physiology and Molecular Biology of Plants, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

Neuroplasticity-Related Genes and Dopamine Receptors Associated with Regional Cortical Thickness Increase Following Electroconvulsive Therapy for Major Depressive Disorder - Gong-Jun Ji; Jiao Li; Wei Liao; Yingru Wang; Lei Zhang; Tongjian Bai; Ting Zhang; Wen Xie; Kongliang He; Chuyan Zhu; Juergen Dukart; Chris Baeken; et al. (Molecular Neurobiology, 2023)

Effects of exogenous carbon and nitrification inhibitors on denitrification rate, product stoichiometry and nirS/nirK-type denitrifiers in a calcareous soil: evidence from 15 N anaerobic microcosm assays - Ting Lan; Mengxiao Li; Xiaoqian He; Junji Yuan; Minghua Zhou; Xiaoyan Tang; Yanyan Zhang; Yang Li; Zhaonan Tian; Xuesong Gao (Journal of Soils and Sediments, 2023)

The Nasal Bacteria Microbiome Comparison Among Fungal Ball Sinusitis, Chronic Sinusitis with Polyps - Pengyu Shi; Hongzheng Wei; Xin Liu; Shouxiang Dong; Shuai He; Yun Zeng; Ting Yang; Chengyao Liu; Yunchuan Li (Indian Journal of Microbiology, 2023)

Associations between short-term and long-term exposure to particulate matter and preterm birth - Yun-Fei Su; Cheng Li; Jing-Jing Xu; Fang-Yue Zhou; Tao Li; Cong Liu; Yan-Ting Wu; He-Feng Huang (Chemosphere, 2023)

High-precision early warning system for rice cadmium accumulation risk assessment - Huili Yan; Hanyao Guo; Ting Li; Hezifan Zhang; Wenxiu Xu; Jianyin Xie; Xiaoyang Zhu; Yijun Yu; Jian Chen; Shouqing Zhao; Jun Xu; Minjun Hu; et al. (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

FSP synthesized core-shell CuOx@SiO2 catalyst with excellent thermal stability for catalytic combustion of ammonia - Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Yu Gui; Xiaochao Wang; Linjia Li; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Template-assisted synthesis of ultrathin graphene aerogels as bifunctional oxygen electrocatalysts for water splitting and alkaline/neutral zinc-air batteries - Qiang Li; Zhifang Sun; Chunyang Yin; Yang Chen; Dingjie Pan; Bingzhe Yu; Yi Zhang; Ting He; Shaowei Chen (Chemical Engineering Journal, 2023)

Artificial skin with fast and robust self-healing ability for durable intelligent protection of magnesium alloys - Lei Liu; Jinglei Lei; Ting Liu; Bo Shang; Xingwang Zhao; Jianxin He; Fusheng Pan; Lingjie Li (Chemical Engineering Journal, 2023)

Effect of electric field and water on Pd-based catalyst for complete oxidation of methane: Study on promotion and deactivation - Xuteng Zhao; Ting Chen; Yinan Wang; Ke Li; Reggie Zhan; He Lin (Chemical Engineering Journal, 2023)

Injectable Host-Guest supramolecular hydrogel Co-Delivers hydrophobic and hydrophilic agents for enhanced wound healing - Jie Xu; Kangning Wang; Yanyan Li; Yue Li; Bingxin Li; Hangqi Luo; Huiling Shi; Xueran Guan; Ting Zhang; Yixiao Sun; Feng Chen; Huacheng He; et al. (Chemical Engineering Journal, 2023)

Maltol ameliorates intervertebral disc degeneration through inhibiting PI3K/AKT/NF-κB pathway and regulating NLRP3 inflammasome-mediated pyroptosis - Yuhang Gong; Jianxing Qiu; Ting Jiang; Ze Li; Weikang Zhang; Xiaohang Zheng; Zixuan He; Weifu Chen; Zhangfu Wang; Xingbing Feng; Meizhen Wang; Zhenghua Hong (Inflammopharmacology, 2023)
Objectives As one of the major causes of low back pain, intervertebral disc degeneration (IDD) has caused a huge problem for humans. Increasing evidence indicates that NLRP3 inflammasome-mediated pyroptosis of NP cells displays an important role in the progression of IDD. Maltol (MA) is a flavoring agent extracted from red ginseng. Due to its anti-inflammatory and antioxidant effects, MA has been widely considered by researchers. Therefore, we hypothesized that MA may be a potential IVD protective agent by regulating NP cells and their surrounding microenvironment. Methods In vitro, qRT-PCR, and Western blot were used to explore the effect of MA on the transcription and protein expression of the anabolic protein (ADAMTS5, MMP3, MMP9) catabolic protein (Aggrecan), and pro-inflammatory factor (iNOS COX-2). Next, the effects of MA on PI3K/AKT/NF-κB pathway and pyroptosis pathway were analyzed by Western blot and immunofluorescence. Molecular docking was used to investigate the relationship between PI3K and MA. Moreover, ELISA was also used to detect the effects of MA on inflammatory factors (TNF-α, PGE2, IL-1β, and IL-18). In vivo, the effects of MA on the vertebral structure of IDD mice were studied by HE and SO staining and the effects of MA on ECM and PI3K/AKT/NF-κB and pyroptosis pathway of IDD mice were studied by immunohistochemical staining. Results MA can ameliorate intervertebral disc degeneration in vivo and in vitro. Specifically, the molecular docking results showed that the binding degree of MA and PI3K was significant. Second, in vitro studies showed that MA inhibited the degradation of ECM and inflammatory response by inhibiting the PI3K/AKT/NF-κB pathway and the pyroptosis mediated by NLRP3 inflammasome, which increased the expression of anabolic proteins, decreased the expression of catabolic proteins, and decreased the secretion of inflammatory mediators such as IL-18 and IL-1β. In addition, according to the study results of the mouse lumbar instability model, MA also improved the tissue disorder and degradation of the intervertebral disc, reduced the loss of proteoglycan and glycosaminoglycan, and inhibited intervertebral disc inflammation, indicating that MA has a protective effect on the intervertebral disc to intervertebral disc in mice. Conclusions Our results suggest that MA slowed IDD development through the PI3K/AKT/NF-κB signaling pathway and NLRP3 inflammasome-mediated pyroptosis, indicating that MA appeared to be a viable medication for IDD treatment.

Cross-biome soil viruses as an important reservoir of virulence genes - Li Bi; Li-Li Han; Shuai Du; Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Hang-Wei Hu (Journal of Hazardous Materials, 2023)

GWAS-assisted genomic prediction of cadmium accumulation in maize kernel with machine learning and linear statistical methods - Huili Yan; Hanyao Guo; Wenxiu Xu; Changhua Dai; Wilson Kimani; Jianyin Xie; Hezifan Zhang; Ting Li; Feng Wang; Yijun Yu; Mi Ma; Zhuanfang Hao; et al. (Journal of Hazardous Materials, 2023)

Clean hydrometallurgical route for highly efficient decontamination and recycling of multiple heavy metals from hazardous Pb smelting residues: Multi-objective leaching optimization, adsorption, and risk assessment - Yu Zhang; Ting Li; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Yulin Pu; Lulu Long; Jinsong He; Wei Zhou; Guoshu Gong; Ling Luo (Journal of Cleaner Production, 2023)

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

Study on the dynamics mechanism of methane diffusion in coal under microwave heating - He Li; Xiaolong Wang; Jiexin Lu; Yi Lu; Shiliang Shi; Zheng Wang; Ting Liu; Qing Ye; Zhenzhen Jia (Fuel, 2023)

Understanding the effect of environment on macrobenthic invertebrate in naturally occurring repeated mesohabitats from the warm-temperate zone river - Amit Jagannath Patil; Zhenhong Wang; Xiaole He; Pangen Li; Ting Yan; He Li (Ecohydrology & Hydrobiology, 2023)

Single-Atom-Catalyzed MXene-Based nanoplatform with Photo-Enhanced Peroxidase-Like activity nanotherapeutics for Staphylococcus aureus infection - ZhangPing Li; Dongqian Xu; Zaian Deng; Jiana Yin; Yuna Qian; Ji-Ting Hou; Xi Ding; Jianliang Shen; Xiaojun He (Chemical Engineering Journal, 2023)

Synergistic effect of F doping and WO3 loading on electrocatalytic oxygen evolution - Ke Lu; Zongyuan Wang; Yaoxin Wu; Xingwu Zhai; Chenxu Wang; Ju Li; Zhimou Wang; Xinyi Li; Yuxuan He; Ting An; Kun Yang; Dezheng Yang; et al. (Chemical Engineering Journal, 2023)

An improved model assessing variation characteristics of pore structure of sandy soil thawing from extremely low temperature using NMR technique - Bo Liu; Yanqing He; Yanhui Han; Ting Li; Dongyang Li; Rong Gao (Cold Regions Science and Technology, 2023)

Identification of major quantitative trait loci and candidate genes for seed weight in soybean - Mengge Xu; Keke Kong; Long Miao; Jianbo He; Tengfei Liu; Kai Zhang; Xiuli Yue; Ting Jin; Junyi Gai; Yan Li (Theoretical and Applied Genetics, 2023)
Key message Four major quantitative trait loci for 100-seed weight were identified in a soybean RIL population under five environments, and the most likely candidate genes underlying these loci were identified. Abstract Seed weight is an important target of soybean breeding. However, the genes underlying the major quantitative trait loci (QTL) controlling seed weight remain largely unknown. In this study, a soybean population of 300 recombinant inbred lines (RILs) derived from a cross between PI595843 (PI) and WH was used to map the QTL and identify candidate genes for seed weight. The RIL population was genotyped through whole genome resequencing, and phenotyped for 100-seed weight under five environments. A total of 38 QTL were detected, and four major QTL, each explained at least 10% of the variation in 100-seed weight, were identified. Six candidate genes within these four major QTL regions were identified by analyses of their tissue expression patterns, gene annotations, and differential gene expression levels in soybean seeds during four developmental stages between two parental lines. Further sequence variation analyses revealed a C to T substitution in the first exon of the Glyma.19G143300 , resulting in an amino acid change between PI and WH, and thus leading to a different predicted kinase domain, which might affect its protein function. Glyma.19G143300 is highly expressed in soybean seeds and encodes a leucine-rich repeat receptor-like protein kinase (LRR-RLK). Its predicted protein has typical domains of LRR-RLK family, and phylogenetic analyses reveled its similarity with the known LRR-RLK protein XIAO ( LOC_Os04g48760 ), which is involved in controlling seed size. The major QTL and candidate genes identified in this study provide useful information for molecular breeding of new soybean cultivars with desirable seed weight.

High Fe and Mn groundwater in the Nanchang, Poyang Lake Basin of China: hydrochemical characteristics and genesis mechanisms - Xiaodong Chu; Zhifei Ma; Daishe Wu; Hao Wang; Jingyuan He; Ting Chen; Ziyin Zheng; Hugang Li; Peng Wei (Environmental Monitoring and Assessment, 2023)

ZmSPO11-2 is critical for meiotic recombination in maize - Menghan Li; Shuyue Li; Yan He; Yan Wang; Ting Zhang; Ping Li; Yan He (Chromosome Research, 2022)

Correction to: Source apportionment and health risk assessment of air pollution particles in eastern district of Chengdu - Yi Huang; Li Wang; Shipeng Zhang; Meng Zhang; Jinjin Wang; Xin Cheng; Ting Li; Min He; Shijun Ni (Environmental Geochemistry and Health, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

A novel bio-washing eluent obtained from fermentation of fruit wastes for removal of soil Pb: efficiency, mechanism, and risk assessment - Xiaomei Pan; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Yun Li; Wei Zhou; Jinsong He; Lulu Long; Ouping Deng; Ling Luo; Guoshu Gong (Environmental Science and Pollution Research, 2022)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Mathematical modeling for mutator phenotype and clonal selection advantage in the risk analysis of lung cancer - Lingling Li; Ting Zhao; Xingshi He; Xinshe Yang; Tianhai Tian; Xinan Zhang (Theory in Biosciences, 2022)

Effects of Cerebellar Transcranial Direct Current Stimulation in Patients with Stroke: a Systematic Review - Li Hong-yu; Zhang Zhi-jie; Li Juan; Xiong Ting; He Wei-chun; Zhu Ning (The Cerebellum, 2022)

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

Particle Design and Inhalation Delivery of Iodine for Upper Respiratory Tract Infection Therapy - Kaikai Zhang; Xiaohong Ren; Jiacai Chen; Caifen Wang; Siyu He; Xiaojin Chen; Ting Xiong; Jiawen Su; Shujun Wang; Weifeng Zhu; Jiwen Zhang; Li Wu (AAPS PharmSciTech, 2022)

Prediction of drought/flood intensities based on a 500-year time series in three different climate provinces of China - Yu Peng; Zhaohua Wang; Yixin Cui; Yali Su; Yiyun Tang; Shiqian Luo; Lianlin Liu; Yanqiu Zhou; Jihui Dong; Wentao Wang; Xiang Li; Jiaxin Shang; et al. (Regional Environmental Change, 2022)

Effects of synthetic nitrification inhibitor (3,4-dimethylpyrazole phosphate; DMPP) and biological nitrification inhibitor (methyl 3-(4-hydroxyphenyl) propionate; MHPP) on the gross N nitrification rate and ammonia oxidizers in two contrasting soils - Ting Lan; Mengxiao Li; Xiaoqian He; Ouping Deng; Wei Zhou; Ling Luo; Guangdeng Chen; Shu Yuan; Jing Ling; Min Zeng; Xuesong Gao (Biology and Fertility of Soils, 2022)

A study of health management of LWD tool based on data-driven and model-driven - Hui Li; Zi-Hua He; Yu-ting Zhang; Jin Feng; Zun-Yi Jian; Yi-Bo Jiang (Acta Geophysica, 2022)

Prediction and validation of cross-protective candidate antigen of Hyalomma asiaticum cathepsin L between H. asiaticum and H. anatolicum - Ruiqi Song; Xuejie Zhai; Xinli Fan; Yongchang Li; Huercha; Ting Ge; Caishan Li; Min Li; Wenwen He; Huizhen Zheng; Lu Gan; Yang Zhang; et al. (Experimental and Applied Acarology, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Transcriptome analysis reveals MYB and WRKY transcription factors involved in banana (Musa paradisiaca AA) magnesium deficiency - Yong Yang; Xinping Li; Baolin Kan; Hongsu He; Ting Li; Yuanhao Ding; Pengmeng Du; Wenjie Lai; Haiyan Hu; Jiaquan Huang (Planta, 2021)

Monochloropropanediol in edible vegetable oils from Hangzhou market in China: occurrence and exposure risk assessment - Ji-Cai Fan; Hua-li He; Ren Ren; Shu-ting Wang (Food Additives & Contaminants: Part A, 2021)

Enhanced SA and Ca2+ signaling results in PCD-mediated spontaneous leaf necrosis in wheat mutant wsl - Huijuan Li; Zhixin Jiao; Peipei Zhang; Yongjing Ni; Ting Wang; Jing Zhang; Junchang Li; Yumei Jiang; Xiwen Yang; Lei Li; Ziping Yao; Jishan Niu; et al. (Molecular Genetics and Genomics, 2021)

Efficiency and comprehensive risk assessment of soil Pb and Cd by washing technique with three biodegradable eluents - Qinmei Zhong; Shirong Zhang; Xiaomei Pan; Guiyin Wang; Xiaoxun Xu; Ting Li; Wei Zhou; Yan He; Ling Luo; Yan Liu; Lulu Long (Environmental Science and Pollution Research, 2021)

Analysis of the Spatial and Temporal Variation of Sea Ice and Connectivity in the NEP of the Arctic in Summer in Hot Years - Guochong Liu; Min Ji; Fengxiang Jin; Ying Li; Yawen He; Ting Li (Journal of Marine Science and Engineering, 2021)
Climate warming has enabled the Arctic region to achieve seasonal navigation, and sea ice concentration is an important factor affecting the navigation of the Arctic waterways. This article uses the Arctic sea ice concentration data of the three highest temperatures in 2016, 2019, and 2020, combined with the Arctic summer sea level pressure, wind field, temperature, temperature anomaly, ice age, and sea ice movement data to analyze the spatial and temporal variation of sea ice and connectivity in the Northeast Passage (NEP) of the Arctic in Summer in three hot years, and summarizes the causes of sea ice anomalies. The results show that: (1) the summer Arctic sea ice extent in 2016, 2019 and 2020 were all lower than the multi-year average sea ice extent, and the summer sea ice extent in 2020 had the largest change trend; (2) in October of these three years, the sea ice was all negative anomalies, extending the opening time of the NEP; (3) when the sea ice concentration was 30% as the threshold, the navigation period of the NEP in 2016 was from mid-August to late October, 2019 was from the beginning of August to mid-October, 2020 was from the end of July to the end of October, and 2020 was the longest year since the opening of the NEP; (4) when the sea ice concentration was 10% as the threshold, the navigation period of the NEP in 2016 was from the end of August to the end of October, 2019 was from early August to mid-October, and 2020 was from the beginning of August to the end of October; (5) the key navigable areas of the NEP in the past three years were the central waters of the East Siberian Sea, the New Siberian Islands and the Vilkitsky Strait; (6) the navigation period of the NEP in 2016, 2019 and 2020 was longer. The main reasons were that the temperature of the NEP in the past 3 years was relatively high, the wind was weak, the sea ice movement had little effect, and the sea ice age in the key navigable areas was first year ice, which was easy to melt, which greatly promoted the opening of the NEP.

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Structure–activity relationship studies on Pd176252 derivatives leading to discovery of novel GRP receptor antagonist with potent anticancer activity - Ming-jun Yu; Chao Li; Meng He; Yu-ting Zhu; Rui Yang; Sheng-song Deng; Xiao-ming Meng; Ri-sheng Yao (Medicinal Chemistry Research, 2021)

Analysis of Sea Ice Timing and Navigability along the Arctic Northeast Passage from 2000 to 2019 - Min Ji; Guochong Liu; Yawen He; Ying Li; Ting Li (Journal of Marine Science and Engineering, 2021)
The ablation of Arctic sea ice makes seasonal navigation possible in the Arctic region, which accounted for the apparent influence of sea ice concentration in the navigation of the Arctic route. This paper uses Arctic sea ice concentration daily data from January 1, 2000, to December 31, 2019. We used a sea ice concentration threshold value of 40% to define the time window for navigating through the Arctic Northeast Passage (NEP). In addition, for the year when the navigation time of the NEP is relatively abnormal, we combined with wind field, temperature, temperature anomaly, sea ice age and sea ice movement data to analyze the sea ice conditions of the NEP and obtain the main factors affecting the navigation of the NEP. The results reveal the following: (1) The sea ice concentration of the NEP varies greatly seasonally. The best month for navigation is September. The opening time of the NEP varies from late July to early September, the end of navigation is concentrated in mid-October, and the navigation time is basically maintained at more than 30 days. (2) The NEP was not navigable in 2000, 2001, 2003 and 2004. The main factors are the high amount of multi-year ice, low temperature and the wind field blowing towards the Vilkitsky Strait and sea ice movement. The navigation time in 2012, 2015 and 2019 was longer, and the driving factors were the high temperature, weak wind and low amount of one-year ice. The navigation time in 2003, 2007 and 2013 was shorter, and the influencing factors were the strong wind field blowing towards the Vilkitsky Strait. (3) The key navigable areas of the NEP are the central part of the East Siberian Sea and the Vilkitsky Strait, and the Vilkitsky Strait has a greater impact on the NEP than the central part of the East Siberian Sea. The main reason for the high concentration of sea ice in the central part of the East Siberian Sea (2000 and 2001) was the large amount of multi-year ice. The main reason for the high concentration of sea ice in the Vilkitsky Strait (2000 to 2004 and 2007, 2013) was the strong offshore wind in summer, all of which were above 4 m s−1, pushing the sea ice near the Vilkitsky Strait to accumulate in the strait, thus affecting the opening of the NEP.

Difference in the binding mechanism of distinct antimony forms in bovine serum albumin - Jiali Gu; Gang Yang; Xiang Li; Qian He; Xiyao Huang; Ting Sun (BioMetals, 2021)

A calculation model of the normal coefficient of restitution based on multi-factor interaction experiments - Zhong-Min Ji; Zhi-Jian Chen; Qing-He Niu; Ting-Hui Wang; Tian-Jun Wang; Tian-Li Chen (Landslides, 2021)

Protein expression pattern of calcium-responsive transactivator in early postnatal and adult testes - Ana Du; Li Li; Zhaoshuang Jiao; Gaochun Zhu; Ting Peng; He Li (Histochemistry and Cell Biology, 2021)
Calcium-responsive transactivator (CREST), a nuclear protein highly expressed in postmitotic neurons, is involved in the regulation of cell cycle, differentiation and dendritic development of neuronal cells. Its mRNA has been detected in the testis of adult rat, whilst its protein expression and distribution pattern in the testis remain to be elucidated. In this study, we examined the distribution of CREST in the adult testes of both rats and human as well as the expression pattern of CREST in the testes of postnatal developing rats. In the adult testes of both human and rats, immunohistochemical analysis revealed that CREST was selectively distributed in the mature Sertoli cells but not in the spermatogenic cells. In the testes of postnatal developmental rats, CREST was expressed not only in Sertoli cells but also in the gonocytes and spermatogenic cells at the initial stage of spermatogenic cell differentiation. CREST immunoreactivity continued to increase in Sertoli cells during differentiation, reaching its peak in adulthood. However, CREST immunostaining intensity dramatically decreased as the spermatogenic cells differentiate, disappearing in the post-differentiation stage. Furthermore, Brg1 and p300, two CREST-interacting proteins ubiquitously expressed in the body, are found to be colocalized with CREST in the spermatogenic epithelial cells including Sertoli cells. The unique expression pattern of CREST in developing testis suggests that CREST might play regulatory roles in the differentiation of spermatogenic epithelial cells. The Sertoli cell-specific expression of CREST in the adulthood hints that CREST might be a novel biomarker for the mature Sertoli cells.

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Characteristics of the potential vorticity and its budget in the surface layer over the Tibetan plateau - Chen Sheng; Guoxiong Wu; Yiqiong Tang; Bian He; Yongkun Xie; Tingting Ma; Ting Ma; Jinxiao Li; Qing Bao; Yimin Liu (International Journal of Climatology, 2021)
The variability of interior atmospheric potential vorticity (PV) is linked with PV generation at the Earth's surface. The present paper reveals the features of the surface PV and provides a stepping stone to investigate the surface PV budget. In this study, the formats of the PV and PV budget adopting a generalized vertical coordinate were theoretically examined to facilitate the calculation of the surface PV and its budget. Results show that the formats of the PV and PV budget equations are independent of the vertical coordinate. While the vertical component of the surface PV dominates over the platform of the Tibetan Plateau, the horizontal component plays an important role over the slopes of the Tibetan Plateau, especially the southern slope owing to the strong in‐situ meridional gradient of the potential temperature. These results indicate that the employment of complete surface PV not only provides a finer PV structure but also more appropriately reveals its effect on atmospheric circulation. Diagnosis based on reanalysis and model output demonstrates that the surface PV budget equation is well balanced both in terms of the climate mean and synoptic process, and the surface PV budget in June has a prominent diurnal cycle. The diabatic heating with a minimum in the early morning and a maximum from evening to midnight contributes dominantly to this diurnal cycle. It is further indicated that positive PV generation due to diabatic heating is essential for the formation, development, and movement of the Tibetan Plateau vortex.

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Determination of phthalate esters in breast milk before and after frozen storage in milk storage bags - Ji-Cai Fan; Ren Ren; Hua-Li He; Quan Jin; Shu-Ting Wang (Food Additives & Contaminants: Part A, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Chemical composition of Erycibe schmidtii and antiproliferative activity of scopoletin on immature dendritic cells - Wang Ren; Yantang Wang; Qinhui He; Yue Zhou; Chunxin Li; Wenling Wang; Xiao Leng; Ting Zeng; Qiang Zou; Limei Li (Natural Product Research, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Annual Characteristics, Source Analysis of PM1-Bound Potentially Harmful Elements in the Eastern District of Chengdu, China - Jinjin Wang; Yi Huang; Ting Li; Huibin Shi; Min He; Xin Cheng; Shijun Ni; Chengjiang Zhang (Archives of Environmental Contamination and Toxicology, 2020)

Source apportionment and health risk assessment of air pollution particles in eastern district of Chengdu - Yi Huang; Li Wang; Shipeng Zhang; Meng Zhang; Jinjin Wang; Xin Cheng; Ting Li; Min He; Shijun Ni (Environmental Geochemistry and Health, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Polyploidization of Plumbago auriculata Lam. in vitro and its characterization including cold tolerance - Yulan Jiang; Shiliang Liu; Ju Hu; Guangti He; Yingqi Liu; Xi Chen; Ting Lei; Qiao Li; Lijuan Yang; Wenji Li; Di Hu; Jiani Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Interactions Between Different Selenium Compounds and Essential Trace Elements Involved in the Antioxidant System of Laying Hens - Xue Lin; Ting Yang; Hua Li; Yinli Ji; Yurong Zhao; Jianhua He (Biological Trace Element Research, 2020)

Phosphate-Solubilizing Pseudomonas sp. Strain P34-L Promotes Wheat Growth by Colonizing the Wheat Rhizosphere and Improving the Wheat Root System and Soil Phosphorus Nutritional Status - Xixi Liu; Xiaoxun Jiang; Xiangyi He; Weirong Zhao; Yuanyuan Cao; Tingting Guo; Ting Li; Haiting Ni; Xinyun Tang (Journal of Plant Growth Regulation, 2019)

Detection of 20 phthalate esters in breast milk by GC-MS/MS using QuEChERS extraction method - Ji-Cai Fan; Ren Ren; Quan Jin; Hua-Li He; Shu-Ting Wang (Food Additives & Contaminants: Part A, 2019)

Vibralactone Z 4 , the first chain-like vibralactone derivative from cultures of the basidiomycete Boreostereum vibrans - Juan He; Kai-Ting Duan; Zheng-Hui Li; Hong-Lian Ai; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

MicroRNA-494 targets PTEN and suppresses PI3K/AKT pathway to alleviate hypertrophic scar formation - Ting He; Yue Zhang; Yang Liu; Hongtao Wang; Wanfu Zhang; Jiaqi Liu; Na Li; Yan Li; Luxu Wang; Songtao Xie; Dahai Hu (Journal of Molecular Histology, 2019)

Biological perchlorate reduction: which electron donor we can choose? - Li He; Yu Zhong; Fubing Yao; Fei Chen; Ting Xie; Bo Wu; Kunjie Hou; Dongbo Wang; Xiaoming Li; Qi Yang (Environmental Science and Pollution Research, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Fine mapping of a novel yellow-green leaf 14 (ygl14) mutant in rice - Jia Tan; Ting Zhang; Saisai Xia; Meng Yan; Fengfei Li; Xianchun Sang; Guanghua He; Yinghua Ling (Euphytica, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Distribution and partitioning of heavy metals in large anthropogenically impacted river, the Pearl River, China - Silan Liu; Zhongwei Wang; Yuanyuan Zhang; Yulong Liu; Wei Yuan; Ting Zhang; Yujie Liu; Ping Li; Li He; Jiubin Chen (Acta Geochimica, 2019)

Identification of key genes relevant to the prognosis of ER-positive and ER-negative breast cancer based on a prognostic prediction system - Bin Xiao; Jianfeng Hang; Ting Lei; Yongyin He; Zhenzhan Kuang; Li Wang; Lidan Chen; Jia He; Weiyun Zhang; Yang Liao; Zhaohui Sun; Linhai Li (Molecular Biology Reports, 2019)

The control of a virtual automatic car based on multiple patterns of motor imagery BCI - Hongtao Wang; Ting Li; Anastasios Bezerianos; Hui Huang; Yuebang He; Peng Chen (Medical & Biological Engineering & Computing, 2019)

Viral metagenomics analysis and eight novel viral genomes identified from the Dushanzi mud volcanic soil in Xinjiang, China - Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Li-Li Han (Journal of Soils and Sediments, 2019)

Abnormal intrinsic cerebro-cerebellar functional connectivity in un-medicated patients with bipolar disorder and major depressive disorder - Yuan He; Ying Wang; Ting-Ting Chang; Yanbin Jia; Junjing Wang; Shuming Zhong; Huiyuan Huang; Yao Sun; Feng Deng; Xiaoyan Wu; Chen Niu; Li Huang; et al. (Psychopharmacology, 2018)

Using Huntingtin Knock-In Minipigs to Fill the Gap Between Mouse Models and Patients with Huntington’s Disease - Xiangqian Liu; Ting Peng; He Li (Neuroscience Bulletin, 2018)

Herp Promotes Degradation of Mutant Huntingtin: Involvement of the Proteasome and Molecular Chaperones - Huanhuan Luo; Liying Cao; Xuan Liang; Ana Du; Ting Peng; He Li (Molecular Neurobiology, 2018)

Negative regulation of MAVS-mediated innate immune response by ASC - Yue Han; Xiang He; Congwen Wei; Ting Song; Ling Zou; Zihui Li; Jiazhou Ye; Lunan Qi; Lequn Li; Hui Zhong; Feixiang Wu (Molecular and Cellular Biochemistry, 2018)

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids - Jiaqi Liu; Huayu Zhu; Hongtao Wang; Jun Li; Fu Han; Yang Liu; Wanfu Zhang; Ting He; Na Li; Zhao Zheng; Dahai Hu (Journal of Molecular Histology, 2018)

Cross-cultural adaption and psychometric properties of the Chinese version of the Diabetes Behavior Rating Scale: a pilot study - Jing Zhu; Jingjing Xu; Yang Chen; Yong Gu; Li Ji; Yufeng Zhou; Min Zhu; Hsiang-Ting Hsu; Xiaoping Huang; Cuiping Yuan; Yun Shi; Dan Yan; et al. (Science China Life Sciences, 2018)

Physiological and biochemical responses of Camellia sinensis to stress associated with Empoasca vitis feeding - Jian-yu Li; Meng-zhu Shi; Jian-wei Fu; Yue-chao He; David J. Perović; Ting Wang (Arthropod-Plant Interactions, 2018)

Assessment of tidal range energy resources based on flux conservation in Jiantiao Bay, China - Min Du; He Wu; Huaming Yu; Ting Lv; Jiangyu Li; Yujun Yu (Journal of Ocean University of China, 2017)

Occurrence and Distribution of Organophosphate Esters in Surface Soil and Street Dust from Chongqing, China: Implications for Human Exposure - Ming-Jing He; Ting Yang; Zhi-Hao Yang; Qi Li; Shi-Qiang Wei (Archives of Environmental Contamination and Toxicology, 2017)

Orexin Directly Enhances the Excitability of Globus Pallidus Internus Neurons in Rat by Co-activating OX1 and OX2 Receptors - He-Ren Gao; Qian-Xing Zhuang; Yong-Xiao Zhang; Zhang-Peng Chen; Bin Li; Xiao-Yang Zhang; Yi-Ting Zhong; Jian-Jun Wang; Jing-Ning Zhu (Neuroscience Bulletin, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Altered functional connectivity within and between the default model network and the visual network in primary open-angle glaucoma: a resting-state fMRI study - Jieqiong Wang; Ting Li; Peng Zhou; Ningli Wang; Junfang Xian; Huiguang He (Brain Imaging and Behavior, 2017)

Molecular adaptation in the world's deepest‐living animal: Insights from transcriptome sequencing of the hadal amphipod Hirondellea gigas - Yi Lan; Jin Sun; Renmao Tian; Douglas H. Bartlett; Runsheng Li; Yue Him Wong; Weipeng Zhang; Jian‐Wen Qiu; Ting Xu; Li‐Sheng He; Harry G. Tabata; Pei‐Yuan Qian (Molecular Ecology, 2017)
The Challenger Deep in the Mariana Trench is the deepest point in the oceans of our planet. Understanding how animals adapt to this harsh environment characterized by high hydrostatic pressure, food limitation, dark and cold is of great scientific interest. Of the animals dwelling in the Challenger Deep, amphipods have been captured using baited traps. In this study, we sequenced the transcriptome of the amphipod Hirondellea gigas collected at a depth of 10,929 m from the East Pond of the Challenger Deep. Assembly of these sequences resulted in 133,041 contigs and 22,046 translated proteins. Functional annotation of these contigs was made using the go and kegg databases. Comparison of these translated proteins with those of four shallow‐water amphipods revealed 10,731 gene families, of which 5659 were single‐copy orthologs. Base substitution analysis on these single‐copy orthologs showed that 62 genes are positively selected in H. gigas , including genes related to β‐alanine biosynthesis, energy metabolism and genetic information processing. For multiple‐copy orthologous genes, gene family expansion analysis revealed that cold‐inducible proteins (i.e., transcription factors II A and transcription elongation factor 1) as well as zinc finger domains are expanded in H. gigas . Overall, our results indicate that genetic adaptation to the hadal environment by H. gigas may be mediated by both gene family expansion and amino acid substitutions of specific proteins.

Derivation of Haploid Neurons from Mouse Androgenetic Haploid Embryonic Stem Cells - He Xu; Chunmei Yue; Ting Zhang; Yuanyuan Li; Ao Guo; Jiaoyang Liao; Gang Pei; Jinsong Li; Naihe Jing (Neuroscience Bulletin, 2017)

DNA hypermethylation of sFRP5 contributes to indoxyl sulfate-induced renal fibrosis - Yanlin Yu; Xu Guan; Ling Nie; Yong Liu; Ting He; Jiachuan Xiong; Xinli Xu; Yan Li; Ke Yang; Yiqin Wang; Yunjian Huang; Bing Feng; et al. (Journal of Molecular Medicine, 2017)

Nr3C1-Bhlhb2 Axis Dysregulation Is Involved in the Development of Attention Deficit Hyperactivity - Li Hui Wu; Wei Cheng; Mei Yu; Bao Mei He; Hui Sun; Qi Chen; Yi Wei Dong; Xiao Ting Shao; Qian Qian Cai; Min Peng; Xing Zhong Wu (Molecular Neurobiology, 2017)

Unique community structure of viruses in a glacier soil of the Tianshan Mountains, China - Li-Li Han; Dan-Ting Yu; Li-Mei Zhang; Jun-Tao Wang; Ji-Zheng He (Journal of Soils and Sediments, 2017)

Antioxidant and antidiabetic properties of tartary buckwheat rice flavonoids after in vitro digestion - Tao Bao; Ye Wang; Yu-ting Li; Vemana Gowd; Xin-he Niu; Hai-ying Yang; Li-shui Chen; Wei Chen; Chong-de Sun (Journal of Zhejiang University-SCIENCE B, 2016)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Levels of five metals in male hair from urban and rural areas of Chongqing, China - Ming-Jing He; Shi-Qiang Wei; Yu-Xin Sun; Ting Yang; Qi Li; Deng-Xiang Wang (Environmental Science and Pollution Research, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Nuclear genetic variation of Rosa odorata var. gigantea (Rosaceae): population structure and conservation implications - Jing Meng; Shui-Lian He; De-Zhu Li; Ting-Shuang Yi (Tree Genetics & Genomes, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

GOLPH3 Mediated Golgi Stress Response in Modulating N2A Cell Death upon Oxygen-Glucose Deprivation and Reoxygenation Injury - Ting Li; Hong You; Xiaoye Mo; Wenfang He; Xiangqi Tang; Zheng Jiang; Shiyu Chen; Yang Chen; Jie Zhang; Zhiping Hu (Molecular Neurobiology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Influence of the Ring Size on the Binding Ability of FTO Investigated by Fluorescence Spectroscopy - Wu He; Zhigang Li; Lingling Yang; Qingwei Jiang; Ting Ren; Lijiao Zhang; Zhenhua Shen; Qinghua Yang; Ruiyong Wang; Junbiao Chang (Journal of Fluorescence, 2015)

HAP1 helps to regulate actin-based transport of insulin-containing granules in pancreatic β cells - Zhiyong Wang; Ting Peng; Hongnian Wu; Jun He; He Li (Histochemistry and Cell Biology, 2015)

Simulation of long-term spring wheat yields, soil organic C, N and water dynamics using DSSAT-CSM in a semi-arid region of the Canadian prairies - Zhuo Ting Li; J. Y. Yang; W. N. Smith; C. F. Drury; R. L. Lemke; B. Grant; W. T. He; Xiao Gang Li (Nutrient Cycling in Agroecosystems, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Stratigraphic framework and microfacies of the Triassic Lower Karamay Formation in districts I, III, NW Junggar, China - Miao He; Zhenkui Jin; Tingdong Li; Xiujuan Guo; Ting Yang (Journal of Earth Science, 2014)

Study of GOLPH3: a Potential Stress-Inducible Protein from Golgi Apparatus - Ting Li; Hong You; Jie Zhang; Xiaoye Mo; Wenfang He; Yang Chen; Xiangqi Tang; Zheng Jiang; Ranran Tu; Liuwang Zeng; Wei Lu; Zhiping Hu (Molecular Neurobiology, 2014)

Visualizing the microtubule-associated protein tau in the nucleus - Jing Lu; Ting Li; RongQiao He; Perry F. Bartlett; Jürgen Götz (Science China Life Sciences, 2014)

Uric formaldehyde levels are negatively correlated with cognitive abilities in healthy older adults - Jing Yu; Tao Su; Ting Zhou; Yingge He; Jing Lu; Juan Li; Rongqiao He (Neuroscience Bulletin, 2014)

Silencing the glycerol-3-phosphate dehydrogenase gene in Saccharomyces cerevisiae results in more ethanol being produced and less glycerol - Wenjin He; Shichao Ye; Ting Xue; Shengyan Xu; Weiyan Li; Jihua Lu; Luoyuan Cao; Bingying Ye; Youqiang Chen (Biotechnology Letters, 2014)

Chondrogenic differentiation and three dimensional chondrogenesis of human adipose-derived stem cells induced by engineered cartilage-derived conditional media - Hengyun Sun; Yu Liu; Ting Jiang; Xia Liu; Aijuan He; Jie Li; Wenjie Zhang; Wei Liu; Yilin Cao; Guangdong Zhou (Tissue Engineering and Regenerative Medicine, 2014)

Left hemiparalexia of Chinese characters: neglect dyslexia or disruption of pathway of visual word form processing? - Wenchao Yi; Ting Wu; Wei Chen; Ti-fei Yuan; Benyan Luo; Chunlei Shan; Jianan Li; Sheng He; Xuchu Weng (Brain Structure and Function, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Introgression of bacterial wilt resistance from eggplant to potato via protoplast fusion and genome components of the hybrids - Yan Yu; Wenxuan Ye; Li He; Xingkui Cai; Ting Liu; Jun Liu (Plant Cell Reports, 2013)

Advances in monoclonal antibody application in myocarditis - Li-na Han; Shuang He; Yu-tang Wang; Li-ming Yang; Si-yu Liu; Ting Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Use of multi-electrode array recordings in studies of network synaptic plasticity in both time and space - Ming-Gang Liu; Xue-Feng Chen; Ting He; Zhen Li; Jun Chen (Neuroscience Bulletin, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

A regional ocean reanalysis system for coastal waters of China and adjacent seas - Guijun Han; Wei Li; Xuefeng Zhang; Dong Li; Zhongjie He; Xidong Wang; Xinrong Wu; Ting Yu; Jirui Ma (Advances in Atmospheric Sciences, 2011)

VP15R from infectious spleen and kidney necrosis virus is a non-muscle myosin-II-binding protein - Xiaopeng Xu; Ting Lin; Lichao Huang; Shaoping Weng; Wei Wei; Zhongsheng Li; Ling Lü; Zhijian Huang; Jianguo He (Archives of Virology, 2011)

Groundwater environmental capacity and its evaluation index - Li Ting Xing; Qiang Wu; Chun He Ye; Nan Ye (Environmental Monitoring and Assessment, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Sevoflurane postconditioning reduces myocardial reperfusion injury in rat isolated hearts via activation of PI3K/Akt signaling and modulation of Bcl-2 family proteins - Li-na Yu; Jing Yu; Feng-jiang Zhang; Mei-juan Yang; Ting-ting Ding; Jun-kuan Wang; Wei He; Tao Fang; Gang Chen; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Cr(III) oxidation coupled with Mn(II) bacterial oxidation in the environment - Ji-Zheng He; You-Ting Meng; Yuan-Ming Zheng; Li-Mei Zhang (Journal of Soils and Sediments, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Prevalence, genetic diversity, and antimicrobial susceptibility profiles of Staphylococcus aureus isolated from bovine mastitis in Zhejiang Province, China - Jian-ping Li; Hai-jian Zhou; Lin Yuan; Ting He; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2009)

Sample clean-up methods, immunoaffinity chromatography and solid phase extraction, for determination of deoxynivalenol and deepoxy deoxynivalenol in swine serum - Jianwei He; Xiu-Zhen Li; Ting Zhou (Mycotoxin Research, 2009)

Interspecific and intraspecific comparisons of ejaculates in the cotton bollworm Helicoverpa armigera and the tobacco budworm H. assulta - Zhao-Qian Teng; Qian He; Hui-Ting Li; Qing-Wen Zhang (Journal of Ethology, 2009)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

Microbial activity and community diversity in a variable charge soil as affected by cadmium exposure levels and time - Jia-li Shentu; Zhen-li He; Xiao-e Yang; Ting-qiang Li (Journal of Zhejiang University-SCIENCE B, 2008)